Polarizing plate, polarizing plate with phase difference layer, and image display device using the same
By using the combination of the iodine transmission suppression layer and the liquid crystal orientation curing layer in the polarizing plate, the problem of changing the ITO resistance value in high temperature and high humidity environment is solved, and the durability and corrosion resistance of the thin polarizing plate are achieved.
Patent Information
- Application Number
- CN202080094258.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-09-25
- Filing Date
- 2020-10-20
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2040-10-20
AI Technical Summary
In high temperature and high humidity environments, the ITO resistance values of thin polarizers and polarizers with phase difference layers are easily changed, resulting in a significant change in the electrode resistance values of the image display device, affecting the durability and reliability of the equipment.
The iodine transmission inhibiting layer coated with the film with an organic solvent solution having a resin is used to control the ITO resistance value rise rate to 100% or less, and combined with the laminated structure of the liquid crystal orientation curing layer, a circular polarization function is formed. Or phase difference layer with elliptical polarization function, inhibits the movement of iodine and the corrosion of electrodes.
Effectively suppress the change in the resistance value of the electrode in high temperature and high humidity environment, improve the durability of the polarizer and the corrosion resistance of the metal components of the image display device, and realize the excellent performance of the extremely thin polarizer in high temperature and high humidity environment. .
Smart Images

Figure CN115190980B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a polarizing plate, a polarizing plate with a phase difference layer, and an image display device using the same. Background Art
[0002] In recent years, image display devices represented by liquid crystal display devices and electroluminescent (EL) display devices (such as organic EL display devices, inorganic EL display devices) have rapidly become popular. Image display devices are representative of the use of polarizing plates and phase difference plates. In practical applications, polarizing plates with phase difference layers formed by integrating polarizing plates and phase difference plates are widely used (for example, Patent Document 1). However, recently, with the increasing demand for thinning of image display devices, the demand for thinning of polarizing plates and polarizing plates with phase difference layers has also increased. However, when thin polarizing plates and polarizing plates with phase difference layers are applied to image display devices, there are cases where the resistance value of the electrodes of the image display device changes significantly under high temperature and high humidity environments.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent No. 3325560 Summary of the invention
[0006] Problem that the invention aims to solve
[0007] The present invention is made to solve the above-mentioned existing problems, and its main purpose is to provide a thin polarizing plate and a polarizing plate with a phase difference layer, which can suppress the change of the resistance value of the electrode in a high temperature and high humidity environment when applied to an image display device.
[0008] Solutions for solving problems
[0009] The polarizing plate of the present invention comprises a polarizer, an iodine transmission suppression layer and an adhesive layer in this order, and has an ITO resistance value increase rate of 100% or less.
[0010] In one embodiment, the iodine transmission inhibiting layer is a solidified or thermally cured coating of an organic solvent solution of a resin. In one embodiment, the resin constituting the iodine transmission inhibiting layer has a glass transition temperature of 85° C. or higher and a weight average molecular weight Mw of 25,000 or higher.
[0011] In one embodiment, two or more iodine transmission suppression layers are provided between the polarizer and the adhesive layer.
[0012] In one embodiment, the iodine transmission suppression layer has a thickness of 0.05 μm to 10 μm.
[0013] In one embodiment, the resin constituting the iodine transmission inhibition layer comprises a copolymer obtained by polymerizing a monomer mixture, and the monomer mixture comprises greater than 50 parts by weight of a (meth)acrylic acid monomer and greater than 0 parts by weight and less than 50 parts by weight of a monomer represented by formula (1):
[0014]
[0015] (wherein, X represents a functional group containing a reactive group, and the reactive group is at least one reactive group selected from the group consisting of a vinyl group, a (meth)acryloyl group, a styryl group, a (meth)acrylamide group, a vinyl ether group, an epoxy group, an oxetane group, a hydroxyl group, an amino group, an aldehyde group and a carboxyl group, and R 1 and R 2 each independently represents a hydrogen atom, an aliphatic hydrocarbon group which may have a substituent, an aryl group which may have a substituent, or a heterocyclic group which may have a substituent, and R 1 and R 2 are optionally linked to each other to form a ring).
[0016] According to another aspect of the present invention, a polarizing plate with a phase difference layer is provided. The polarizing plate with a phase difference layer comprises the above-mentioned polarizing plate and the phase difference layer disposed between the above-mentioned polarizer and the above-mentioned adhesive layer. The phase difference layer is an oriented solidified layer of a liquid crystal compound having a circular polarization function or an elliptically polarizing function. The ITO resistance value increase rate of the polarizing plate with a phase difference layer is less than 100%.
[0017] In one embodiment, the phase difference layer is a single layer, and Re(550) of the phase difference layer is 100nm-190nm, and the angle formed by the slow axis of the phase difference layer and the absorption axis of the polarizer is 40°-50°.
[0018] In one embodiment, the phase difference layer has a stacked structure of an orientation solidified layer of a first liquid crystal compound and an orientation solidified layer of a second liquid crystal compound; the Re(550) of the orientation solidified layer of the first liquid crystal compound is 200nm~300nm, and the angle formed by its slow axis and the absorption axis of the polarizer is 10°~20°; the Re(550) of the orientation solidified layer of the second liquid crystal compound is 100nm~190nm, and the angle formed by its slow axis and the absorption axis of the polarizer is 70°~80°.
[0019] In one embodiment, the total thickness of the polarizing plate with a retardation layer is 60 μm or less.
[0020] According to another aspect of the present invention, there is provided an image display device comprising the above-mentioned polarizing plate or the polarizing plate with a retardation layer.
[0021] In one embodiment, the image display device is an organic electroluminescent display device or an inorganic electroluminescent display device.
[0022] Effects of the Invention
[0023] According to an embodiment of the present invention, by setting a specific iodine transmission inhibition layer to control the ITO resistance value increase rate to be below a specified value, a thin polarizing plate and a polarizing plate with a phase difference layer that can suppress the change in the resistance value of the electrode under a high temperature and high humidity environment when applied to an image display device can be realized. The iodine transmission inhibition layer that can be used in the embodiment of the present invention is a solidified product or a thermosetting product of a coating film of an organic solvent solution of a resin, and the glass transition temperature of the resin constituting the iodine transmission inhibition layer is above 85°C, and the weight average molecular weight Mw is above 25,000, and the ITO resistance value increase rate of the embodiment of the present invention is below 100%. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a schematic cross-sectional view of a polarizing plate according to one embodiment of the present invention.
[0025] Figure 2A This is a schematic cross-sectional view of a polarizing plate with a retardation layer according to one embodiment of the present invention.
[0026] Figure 2B This is a schematic cross-sectional view of a polarizing plate with a retardation layer according to another embodiment of the present invention.
[0027] Figure 3 This is a schematic cross-sectional view of a polarizing plate with a retardation layer according to still another embodiment of the present invention.
[0028] Figure 4 This is a schematic cross-sectional view of a polarizing plate with a retardation layer according to still another embodiment of the present invention.
[0029] Figure 5 This is a schematic cross-sectional view of a polarizing plate with a retardation layer according to still another embodiment of the present invention.
[0030] Figure 6 This is a schematic cross-sectional view of a polarizing plate with a retardation layer according to still another embodiment of the present invention. DETAILED DESCRIPTION
[0031] Embodiments of the present invention will be described below, but the present invention is not limited to these embodiments.
[0032] (Definition of terms and symbols)
[0033] The definitions of terms and symbols in this specification are as follows.
[0034] (1) Refractive index (nx, ny, nz)
[0035] “nx” is the refractive index in the direction where the in-plane refractive index reaches the maximum (ie, the slow axis direction), “ny” is the refractive index in the direction orthogonal to the slow axis (ie, the fast axis direction) in the plane, and “nz” is the refractive index in the thickness direction.
[0036] (2) In-plane phase difference (Re)
[0037] "Re(λ)" is the in-plane phase difference measured at 23°C with light of wavelength λnm. For example, "Re(550)" is the in-plane phase difference measured at 23°C with light of wavelength 550nm. When the thickness of the layer (film) is d(nm), Re(λ) is calculated by the formula: Re(λ) = (nx-ny)×d.
[0038] (3) Retardation in the thickness direction (Rth)
[0039] "Rth(λ)" is the phase difference in the thickness direction measured at 23°C with light of wavelength λnm. For example, "Rth(550)" is the phase difference in the thickness direction measured at 23°C with light of wavelength 550nm. When the thickness of the layer (film) is d(nm), Rth(λ) is calculated by the formula: Rth(λ) = (nx-nz)×d.
[0040] (4) Nz coefficient
[0041] The Nz coefficient can be obtained by Nz=Rth / Re.
[0042] (5) Angle
[0043] When an angle is mentioned in this specification, the angle includes both the clockwise direction and the counterclockwise direction relative to a reference direction. Therefore, for example, "45°" means ±45°.
[0044] A.Polarizing plate
[0045] A-1. Overall structure of polarizing plate
[0046] Figure 1 Schematic cross-sectional view of a polarizing plate according to an embodiment of the present invention. The polarizing plate 10 typically has a protective layer 12, a polarizer 11, an iodine transmission inhibition layer 40 and an adhesive layer 30 in sequence. Another protective layer (not shown) may also be provided on the side of the polarizer 11 opposite to the protective layer 12 according to the purpose. The adhesive layer 30 is provided as the outermost layer, and the polarizing plate can be attached to an image display device (substantially an image display unit). The polarizing plate can be used as a polarizing plate on the visual recognition side in the image display device, and can also be used as a polarizing plate on the back side.
[0047] In an embodiment of the present invention, an iodine transmission inhibition layer 40 is provided between the polarizer 11 and the adhesive layer 30 as described above. The iodine transmission inhibition layer is typically a solidified product or a thermosetting product of a coating film of an organic solvent solution of a resin. Furthermore, the glass transition temperature (Tg) of the resin constituting the iodine transmission inhibition layer is, for example, above 85°C, and the weight average molecular weight Mw is, for example, above 25,000. By providing such an iodine transmission inhibition layer at a predetermined position of the polarizer, the iodine in the polarizer can be significantly inhibited from moving to the image display device (substantially the image display unit) under a high temperature and high humidity environment. As a result, a thin polarizing plate (described later in detail) can be realized that can inhibit the change in the resistance value of the electrode under a high temperature and high humidity environment when applied to an image display device. Furthermore, such a polarizing plate can have excellent durability under a high temperature and high humidity environment. Moreover, when the polarizing plate is applied to an image display device, the corrosion of the metal components (such as electrodes, sensors, wiring, and metal layers) of the image display device can be significantly inhibited, and the increase in reflectivity under a high temperature and high humidity environment can be inhibited. Such an effect is a unique effect of a thin polarizing plate. That is, the inventors of the present invention have newly discovered the following problem: when a thin polarizing plate is applied to an image display device, the resistance value of the electrode may increase under a high temperature and high humidity environment, and have found that such a problem is caused by iodine. As a result, repeated studies have been conducted, and it has been found that as a means of preventing iodine from moving to the image display device (essentially an image display unit), it is useful to provide an iodine transmission inhibition layer as described above (a solidified layer or a thermally cured layer of a coating film of an organic solvent solution of a resin having a specific Tg and Mw) so that the ITO resistance value increase rate (described later) is 100% or less, thereby completing the present invention. Furthermore, as described later, the iodine transmission inhibition layer can be formed to be very thin, and by providing the iodine transmission inhibition layer, the protective layer on the opposite side to the visual recognition side can be omitted, so that through these synergistic effects, it can also contribute to further thinning of the polarizing plate.
[0048] In the polarizing plate with a phase difference layer, two or more iodine transmission suppression layers (for example Figure 5 and Figure 6 ). When the polarizing plate with a phase difference layer has two or more iodine transmission suppression layers, the corrosion of metal components can be significantly suppressed when the polarizing plate with a phase difference layer is applied to an image display device.
[0049] Figure 5 In the polarizing plate with a retardation layer shown, two iodine transmission suppression layers are provided between the polarizer and the adhesive layer. Figure 5In the example shown, two iodine transmission suppression layers are provided, between the polarizer 11 and the phase difference layer 20 and between the phase difference layer 20 and the adhesive layer 30. In one embodiment, the iodine transmission suppression layer is provided adjacent to the polarizer. In another embodiment, the iodine transmission suppression layer is provided adjacent to the phase difference layer. In this specification, "adjacent" means directly stacked without the aid of an adhesive layer or the like.
[0050] Figure 6 In the polarizing plate with a phase difference layer shown in the figure, three iodine transmission suppression layers are provided between the polarizer and the adhesive layer. Figure 6 In the example shown, two iodine transmission suppression layers are provided between the polarizer 11 and the phase difference layer 20, and one layer is provided between the phase difference layer 20 and the adhesive layer 30. One of the two iodine transmission suppression layers between the polarizer 11 and the phase difference layer 20 is provided adjacent to the polarizer, and the other is provided adjacent to the phase difference layer.
[0051] In the polarizing plate with phase difference layer, the iodine transmission inhibition layer may be 4 or more layers (e.g., 4 layers, 5 layers, 6 layers). The more iodine transmission inhibition layers there are, the more metal corrosion inhibition effect can be improved. The number of iodine transmission inhibition layers can be set in consideration of cost, manufacturing efficiency, the total thickness of the polarizing plate with phase difference layer, etc.
[0052] In an embodiment of the present invention, as described above, the ITO resistance value increase rate is less than 100%. The ITO resistance value increase rate is preferably less than 70%, more preferably less than 60%, further preferably less than 50%, and particularly preferably less than 45%. The smaller the ITO resistance value increase rate, the more preferred it is, and ideally it is zero, and its lower limit may be, for example, 5%. The ITO resistance value increase rate is an indicator of the ability to suppress the increase in electrode resistance value of the polarizing plate under a high temperature and high humidity environment, and the smaller the value, the better the ability. The ITO resistance value increase rate can be obtained by bonding the polarizing plate to the surface of the ITO layer of the ITO layer / alkali-free glass laminate, and the resistance value of the ITO layer before and after the reliability test (placed in an environment of 60°C·95%RH for 240 hours, and then placed in an environment of 23°C·55%RH for 24 hours) can be obtained using the following formula.
[0053] Resistance increase rate (%) = {(resistance after reliability test - initial resistance) / (initial resistance)} × 100
[0054] In an embodiment of the present invention, the iodine presence index of the adhesive layer 30 is, for example, less than 0.050, preferably less than 0.040, more preferably less than 0.030, further preferably less than 0.020, and particularly preferably less than 0.015. The smaller the iodine presence index, the more preferred it is, and ideally it is zero, and its lower limit may be, for example, 0.001. The iodine presence index is an index of the amount of iodine that moves from the polarizer to the adhesive layer under a high temperature and high humidity environment, and the smaller the index, the smaller the change in the amount of iodine in the polarizer is blocked by the iodine penetration inhibition layer. Therefore, as long as the iodine presence index is within such a range, the movement of iodine can be suppressed, and when the polarizing plate is applied to an image display device, the change in the resistance value of the electrode under a high temperature and high humidity environment can be suppressed, and the excellent durability of the thin polarizing plate under a high temperature and high humidity environment can be achieved. The iodine presence index is obtained by performing secondary ion mass spectrometry (TOF-SIMS) on the polarizing plate after the reliability test (placed in an environment of 85°C and 85% RH for 240 hours, and then placed in an environment of 23°C and 55% RH for 24 hours). More specifically, the iodine presence index can be obtained by performing TOF-SIMS measurement on the surface of the adhesive layer after the reliability test, and selecting C3H3O2 derived from acrylic acid (adhesive) from the negative secondary ions obtained. - The ion intensity of (m / z=71) and I derived from iodine - The ion intensity of (m / z=127) was calculated using the following formula.
[0055] Iodine presence index = I - Ionic strength / C3H3O2 - Ionic Strength
[0056] It should be noted that the adhesive layer 30 can adopt a configuration well-known in the industry, and therefore, description of the detailed configuration of the adhesive layer is omitted.
[0057] The polarizing plate of the embodiment of the present invention may be in the form of a single sheet or in the form of an elongated strip. In this specification, the term "elongated strip" refers to an elongated shape that is sufficiently long relative to the width, for example, including an elongated shape that is 10 times or more, preferably 20 times or more, longer than the width. The elongated polarizing plate may be rolled into a roll.
[0058] The total thickness of the polarizing plate is preferably less than 45 μm, more preferably less than 40 μm, further preferably less than 35 μm, and particularly preferably less than 30 μm. The lower limit of the total thickness may be, for example, 22 μm. According to an embodiment of the present invention, such an extremely thin polarizing plate can be achieved, and further, when such an extremely thin polarizing plate is applied to an image display device, the change in the resistance value of the electrode under a high temperature and high humidity environment can be suppressed, and such an extremely thin polarizing plate can achieve excellent durability under a high temperature and high humidity environment. In addition, such a polarizing plate may have extremely excellent flexibility and bending durability. Therefore, such a polarizing plate is particularly suitable for curved image display devices and / or bendable or foldable image display devices. It should be noted that the so-called total thickness of the polarizing plate refers to the total thickness of the polarizer, the protective layer, the iodine transmission inhibition layer, and the adhesive layer or adhesive layer used to stack them (that is, the total thickness of the polarizing plate does not include the thickness of the adhesive layer 30 and the release film that can be temporarily bonded to its surface).
[0059] In practical applications, it is preferred that a release film is temporarily bonded to the surface of the adhesive layer 30 until the polarizing plate is used. By temporarily bonding the release film, a roll of the polarizing plate can be formed while protecting the adhesive layer.
[0060] A-2. Polarizer
[0061] The polarizer is typically composed of a polyvinyl alcohol (PVA) resin film containing a dichroic substance. The thickness of the polarizer is preferably 1 μm to 8 μm, more preferably 1 μm to 7 μm, and further preferably 2 μm to 5 μm. As long as the thickness of the polarizer is within this range, it can contribute greatly to the thinning of the polarizing plate. Furthermore, in a thin polarizing plate using such a polarizer, the effect of the present invention is significant.
[0062] The boric acid content of the polarizer is preferably 10% by weight or more, more preferably 13% by weight to 25% by weight. As long as the boric acid content of the polarizer is within such a range, the ease of curling adjustment during lamination can be well maintained and the curling during heating can be well suppressed by the synergistic effect with the iodine content described later, while improving the durability of the appearance during heating. The boric acid content can be calculated, for example, by the neutralization method using the following formula as the amount of boric acid contained in the polarizer per unit weight.
[0063]
[0064] The iodine content of the polarizer is preferably 2% by weight or more, more preferably 2% to 10% by weight. When the iodine content of the polarizer is within such a range, the synergistic effect with the boric acid content can well maintain the ease of curling adjustment during lamination, well suppress curling during heating, and improve the durability of appearance during heating. In this specification, "iodine content" refers to the amount of total iodine contained in the polarizer (PVA-based resin film). More specifically, in the polarizer, iodine is present in the form of iodide ions (I - ), iodine molecules (I2), polyiodide ions (I3 - 、I5 - ) and other forms, the iodine content in this specification refers to the amount of iodine in all these forms. The iodine content can be calculated, for example, by the standard curve method of fluorescent X-ray analysis. It should be noted that polyiodide ions exist in the polarizer in the form of PVA-iodine complex. By forming such a complex, absorption dichroism is exhibited in the wavelength range of visible light. Specifically, the complex of PVA and triiodide ion (PVA·I3 - ) has an absorption peak near 470nm, and the complex of PVA and pentaiodide ion (PVA·I5 - ) has an absorption peak near 600 nm. As a result, polyiodide ions can absorb light in a wide range of visible light depending on their form. On the other hand, iodide ions (I - ) has an absorption peak near 230nm and does not substantially interfere with the absorption of visible light. Therefore, the polyiodide ions present in the form of a complex with PVA mainly interfere with the absorption performance of the polarizer.
[0065] The polarizer preferably shows absorption dichroism at any wavelength of 380nm to 780nm. The single transmittance Ts of the polarizer is preferably 40% to 48%, more preferably 41% to 46%. The polarization degree P of the polarizer is preferably 97.0% or more, more preferably 99.0% or more, and further preferably 99.9% or more. The above-mentioned single transmittance is representatively the Y value obtained by measuring with an ultraviolet visible spectrophotometer and correcting for the sensitivity. The above-mentioned polarization degree is representatively obtained by the following formula based on the parallel transmittance Tp and the orthogonal transmittance Tc obtained by measuring with an ultraviolet visible spectrophotometer and correcting for the sensitivity.
[0066] Polarization degree (%) = {(Tp-Tc) / (Tp+Tc)} 1 / 2 ×100
[0067] The polarizer can be typically made using a laminate of more than two layers. As a specific example of a polarizer obtained using a laminate, there can be cited a polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating the resin substrate. The polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating the resin substrate can be made, for example, in the following manner: a PVA-based resin solution is applied to a resin substrate and dried to form a PVA-based resin layer on the resin substrate, thereby obtaining a laminate of the resin substrate and the PVA-based resin layer; the laminate is stretched and dyed to make the PVA-based resin layer into a polarizer. Stretching typically includes immersing the laminate in an aqueous boric acid solution and stretching it. Furthermore, as needed, stretching may further include stretching the laminate in the air at a high temperature (e.g., above 95°C) before stretching in an aqueous boric acid solution. The obtained laminate of resin substrate / polarizer can be used directly (that is, the resin substrate can be used as a protective layer of polarizer), or the resin substrate can be peeled off from the laminate of resin substrate / polarizer and any appropriate protective layer can be laminated on the peeling surface according to the purpose. The details of the manufacturing method of such a polarizer are described in, for example, Japanese Patent Publication No. 2012-73580 and Japanese Patent No. 6470455. The entire contents of these publications are cited in this specification as a reference.
[0068] The manufacturing method of the polarizer typically includes: forming a polyvinyl alcohol resin layer containing a halide and a polyvinyl alcohol resin on one side of a long thermoplastic resin substrate to form a laminate; and sequentially subjecting the laminate to an air auxiliary stretching treatment, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment, wherein the drying shrinkage treatment is performed by heating the laminate while conveying it along the long side direction so that the laminate shrinks by more than 2% in the width direction. Thus, a very thin polarizer having excellent optical properties and suppressed uneven optical properties can be provided. That is, by introducing auxiliary stretching, the crystallinity of PVA can be improved even when PVA is coated on a thermoplastic resin, and high optical properties can be achieved. In addition, by simultaneously improving the orientation of PVA in advance, problems such as a decrease in orientation or dissolution of PVA when immersed in water in subsequent dyeing and stretching processes can be prevented, and high optical properties can be achieved. Furthermore, when the PVA-based resin layer is immersed in a liquid, the orientation disorder of the polyvinyl alcohol molecules and the decrease in orientation can be suppressed compared to the case where the PVA-based resin layer does not contain a halide. As a result, the optical properties of the polarizer obtained by the treatment process of immersing the laminate in a liquid such as dyeing treatment and underwater stretching treatment can be improved. Furthermore, the optical properties can be improved by shrinking the laminate in the width direction through a drying shrinkage treatment.
[0069] A-3. Protective layer
[0070] The protective layer 12 is formed by any appropriate film that can be used as a protective layer of a polarizer. Specific examples of the material as the main component of the film include cellulose resins such as triacetyl cellulose (TAC), polyester resins, polyvinyl alcohol resins, polycarbonate resins, polyamide resins, polyimide resins, polyethersulfone resins, polysulfone resins, polystyrene resins, polynorbornene resins, polyolefin resins, (meth) acrylic resins, acetate resins, and the like. In addition, thermosetting resins or ultraviolet curing resins such as (meth) acrylic resins, carbamate resins, (meth) acrylic carbamate resins, epoxy resins, and silicone resins can also be cited. In addition, for example, glassy polymers such as siloxane polymers can also be cited. In addition, polymer films described in Japanese Patent Publication No. 2001-343529 (WO01 / 37007) can also be used. As the material of the film, for example, a resin composition containing a thermoplastic resin having a substituted or unsubstituted imide group in the side chain and a thermoplastic resin having a substituted or unsubstituted phenyl group and a nitrile group in the side chain can be used, for example, a resin composition containing an alternating copolymer formed by isobutylene and N-methylmaleimide and an acrylonitrile-styrene copolymer can be mentioned. The polymer film can be, for example, an extrusion molding of the above resin composition.
[0071] In one embodiment, the polarizing plate is configured on the visual recognition side of the image display device, and the protective layer 12 is representatively configured on its visual recognition side. In such a case, the protective layer 12 may also be subjected to surface treatments such as hard coating, anti-reflection, anti-adhesion, and anti-glare as needed. Furthermore / or, the protective layer 12 may also be subjected to treatments for improving visual recognition during visual recognition through polarized sunglasses as needed (representatively, imparting (elliptical) circular polarization function and imparting ultra-high phase difference). By implementing such a treatment, even when visually identifying the display screen through polarized lenses such as polarized sunglasses, excellent visual recognition can still be achieved. Therefore, the polarizing plate may also be suitable for image display devices that can be used outdoors.
[0072] The thickness of the protective layer is preferably 10 μm to 50 μm, and more preferably 10 μm to 30 μm. When the surface treatment is performed, the thickness of the outer protective layer is the thickness including the thickness of the surface treatment layer.
[0073] A-4. Iodine permeation inhibition layer
[0074] As described above, the iodine permeation inhibition layer is a solidified product or a thermosetting product of a coating film of an organic solvent solution of a resin. As long as it is such a structure, the thickness can be made very thin (for example, less than 10 μm). The thickness of the iodine permeation inhibition layer is preferably 0.05 μm to 10 μm, more preferably 0.08 μm to 5 μm, further preferably 0.1 μm to 1 μm, and particularly preferably 0.2 μm to 0.7 μm. Furthermore, as long as it is such a structure, the iodine permeation inhibition layer can be directly (that is, without the aid of an adhesive layer or an adhesive layer) formed on the polarizer. According to an embodiment of the present invention, as described above, the polarizer and the iodine permeation inhibition layer are very thin, and the adhesive layer or adhesive used to laminate the iodine permeation inhibition layer can be omitted, so the total thickness of the polarizing plate can be made extremely thin. Furthermore, since the hygroscopicity and moisture permeability of such an iodine permeation inhibition layer are smaller than those of a solidified product of a water-based coating film such as an aqueous solution or an aqueous dispersion, it has the advantage of excellent humidification durability. As a result, a polarizing plate with excellent durability that can maintain optical properties even under high temperature and high humidity environment can be realized. In addition, such iodine transmission inhibition layer, for example, can suppress ultraviolet irradiation from causing adverse effects on polarizing plate (polarizer) compared with the cured product of ultraviolet curable resin. The iodine transmission inhibition layer is preferably a solidified product of a coating film of an organic solvent solution of a resin. The solidified product has a small shrinkage during film forming compared with the cured product, and does not contain residual monomers, etc., so the deterioration of the film itself can be suppressed and the residual monomers, etc. can be suppressed from causing adverse effects on polarizing plate (polarizer).
[0075] Furthermore, the glass transition temperature (Tg) of the resin constituting the iodine transmission inhibition layer is, for example, above 85°C, and the weight average molecular weight Mw is, for example, above 25,000. As long as the Tg and Mw of the resin are within such a range, the synergistic effect of the effect of the iodine transmission inhibition layer formed by the solidified or thermosetting material of the coating film of the organic solvent solution of the resin, even if it is very thin, can still significantly inhibit the movement of iodine in the polarizer to the adhesive layer (ultimately the image display unit). As a result, when the polarizing plate is applied to the image display device, the change in the resistance value of the electrode under high temperature and high humidity environment can be suppressed, and the extremely thin polarizing plate can achieve excellent durability under high temperature and high humidity environment. The Tg of the resin is preferably above 90°C, more preferably above 100°C, further preferably above 110°C, and particularly preferably above 120°C. The upper limit of Tg can be, for example, 200°C. In addition, the Mw of the resin is preferably above 30,000, more preferably above 35,000, and further preferably above 40,000. The upper limit of Mw may be 150,000, for example.
[0076] As the resin constituting the iodine permeation inhibition layer, any appropriate thermoplastic resin or thermosetting resin can be used as long as it can form a solidified product or a thermosetting product of a coating film of an organic solvent solution and has the Tg and Mw as described above. Preferably, it is a thermoplastic resin. As thermoplastic resins, for example, acrylic resins and epoxy resins can be cited. Acrylic resins and epoxy resins can also be used in combination. Representative examples of acrylic resins and epoxy resins that can be used for the iodine permeation inhibition layer are described below.
[0077] Acrylic resins typically contain repeating units derived from (meth)acrylate monomers having a linear or branched structure as the main component. In this specification, (meth)acrylic acid refers to acrylic acid and / or methacrylic acid. Acrylic resins may contain repeating units derived from any appropriate comonomer used according to the purpose. As comonomers, for example, carboxyl-containing monomers, hydroxyl-containing monomers, amide-containing monomers, aromatic ring-containing (meth)acrylates, and heterocyclic vinyl monomers can be cited. By appropriately setting the type, quantity, combination, copolymerization ratio, etc. of the monomer units, an acrylic resin having the above-specified Mw can be obtained.
[0078] <Boron-containing acrylic resin>
[0079] In one embodiment, the acrylic resin includes a copolymer obtained by polymerizing a monomer mixture containing more than 50 parts by weight of a (meth)acrylic monomer and more than 0 parts by weight and less than 50 parts by weight of a monomer represented by formula (1) (hereinafter sometimes referred to as a comonomer).
[0080]
[0081] (wherein, X represents a functional group containing a reactive group, and the reactive group is at least one reactive group selected from the group consisting of a vinyl group, a (meth)acryloyl group, a styryl group, a (meth)acrylamide group, a vinyl ether group, an epoxy group, an oxetane group, a hydroxyl group, an amino group, an aldehyde group, and a carboxyl group, and R 1 and R 2 each independently represents a hydrogen atom, an aliphatic hydrocarbon group which may have a substituent, an aryl group which may have a substituent, or a heterocyclic group which may have a substituent, and R 1 and R 2 are optionally linked to each other to form a ring).
[0082] Boron-containing acrylic resin is representative of the repeating unit shown in the following formula. By polymerizing the monomer mixture of the comonomer and (meth) acrylic monomer shown in the formula (1), the boron-containing acrylic resin has a substituent containing boron in the side chain (for example, the repeating unit of k in the following formula). Thus, when the iodine is transmitted through the suppression layer and the polarizer are adjacent and configured, the adhesion with the polarizer will be improved. The substituent containing boron can be continuously (that is, in a block shape) included in the boron-containing acrylic resin, or it can be randomly included in the boron-containing acrylic resin.
[0083]
[0084] (Where R 6 represents an arbitrary functional group, and j and k represent integers greater than 1).
[0085] <(Meth)acrylic acid monomer>
[0086] As the (meth)acrylic acid-based monomer, any appropriate (meth)acrylic acid-based monomer may be used, and examples thereof include (meth)acrylic acid ester-based monomers having a linear or branched structure and (meth)acrylic acid ester-based monomers having a cyclic structure.
[0087] As the (meth)acrylate monomer having a linear or branched structure, for example, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, methyl 2-ethylhexyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, etc. can be mentioned. Methyl (meth)acrylate is preferably used. Only one (meth)acrylate monomer may be used, or two or more may be used in combination.
[0088] Examples of the (meth)acrylate monomer having a cyclic structure include cyclohexyl (meth)acrylate, benzyl (meth)acrylate, isobornyl (meth)acrylate, 1-adamantyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, dicyclopentyl (meth)acrylate, biphenyl (meth)acrylate, o-biphenyloxyethyl (meth)acrylate, o-biphenyloxyethoxyethyl (meth)acrylate, m-biphenyloxyethyl acrylate, and p-biphenyloxyethyl (meth)acrylate. , ortho-biphenyloxy-2-hydroxypropyl (meth) acrylate, p-biphenyloxy-2-hydroxypropyl (meth) acrylate, m-biphenyloxy-2-hydroxypropyl (meth) acrylate, N-(meth) acryloyloxyethyl-ortho-biphenyl = carbamate, N-(meth) acryloyloxyethyl-p-biphenyl = carbamate, N-(meth) acryloyloxyethyl-m-biphenyl = carbamate, monomers containing biphenyl such as ortho-phenylphenol glycidyl ether acrylate, terphenyl (meth) acrylate, ortho-terphenyloxyethyl (meth) acrylate, etc. Preferably, 1-adamantyl (meth) acrylate and dicyclopentyl (meth) acrylate are used. By using these monomers, a polymer with a high glass transition temperature can be obtained. These monomers can be used alone or in combination of two or more.
[0089] In addition, a silsesquioxane compound having a (meth)acryloyl group can also be used to replace the above-mentioned (meth)acrylate monomer. By using a silsesquioxane compound, an acrylic polymer with a high glass transition temperature is obtained. Silsesquioxane compounds with skeletons such as various skeleton structures, such as cage structures, ladder structures, and random structures are known. The silsesquioxane compound may have only one of these structures, or may have two or more. The silsesquioxane compound may be used only one, or two or more may be used in combination.
[0090] As the silsesquioxane compound containing a (meth)acryloyl group, for example, MAC grade and AC grade of the SQ series of Toagosei Co., Ltd. can be used. MAC grade is a silsesquioxane compound containing a methacryloyl group, and specifically, for example, MAC-SQ TM-100, MAC-SQ SI-20, MAC-SQ HDM, etc. can be mentioned. AC grade is a silsesquioxane compound containing an acryl group, and specifically, for example, AC-SQ TA-100, AC-SQ SI-20, etc. can be mentioned.
[0091] The (meth)acrylic acid-based monomer is used in an amount of more than 50 parts by weight based on 100 parts by weight of the monomer mixture.
[0092] <Comonomer>
[0093] As the comonomer, a monomer represented by the above formula (1) is used. By using such a comonomer, a substituent containing boron is introduced into the side chain of the obtained polymer. The comonomer may be used alone or in combination of two or more.
[0094] Examples of the aliphatic hydrocarbon group in the above formula (1) include a linear or branched alkyl group having 1 to 20 carbon atoms and optionally having a substituent, a cyclic alkyl group having 3 to 20 carbon atoms and optionally having a substituent, and an alkenyl group having 2 to 20 carbon atoms. Examples of the above aryl group include a phenyl group having 6 to 20 carbon atoms and optionally having a substituent, a naphthyl group having 10 to 20 carbon atoms and the like. Examples of the heterocyclic group include a 5-membered or 6-membered cyclic group containing at least one heteroatom and optionally having a substituent. It should be noted that R 1 and R 2 They are optionally linked to each other to form a ring. 1 and R 2 It is preferably a hydrogen atom or a linear or branched alkyl group having 1 to 3 carbon atoms, and more preferably a hydrogen atom.
[0095] The reactive group included in the functional group represented by X is at least one selected from the group consisting of vinyl, (meth)acryloyl, styryl, (meth)acrylamide, vinyl ether, epoxy, oxetane, hydroxyl, amino, aldehyde, and carboxyl. Preferably, the reactive group is (meth)acryloyl and / or (meth)acrylamide. By having these reactive groups, when the iodine transmission suppression layer is arranged adjacent to the polarizer, the adhesion with the polarizer is further improved.
[0096] In one embodiment, the functional group represented by X is preferably a functional group represented by ZY-. Here, Z represents a functional group containing at least one reactive group selected from the group consisting of vinyl, (meth)acryloyl, styryl, (meth)acrylamide, vinyl ether, epoxy, oxetane, hydroxyl, amino, aldehyde and carboxyl groups, and Y represents a phenylene group or an alkylene group.
[0097] Specifically, the following compounds can be used as the comonomer.
[0098]
[0099] The comonomer is used in an amount greater than 0 parts by weight and less than 50 parts by weight relative to 100 parts by weight of the monomer mixture, preferably greater than 0.01 parts by weight and less than 50 parts by weight, more preferably 0.05 to 20 parts by weight, further preferably 0.1 to 10 parts by weight, and particularly preferably 0.5 to 5 parts by weight.
[0100] <Acrylic resin containing lactone ring or the like>
[0101] In another embodiment, the acrylic resin has a repeating unit containing a ring structure selected from a lactone ring unit, a glutaric anhydride unit, a glutarimide unit, a maleic anhydride unit, and a maleimide (N-substituted maleimide) unit. The repeating unit of the acrylic resin may contain only one type of repeating unit containing a ring structure, or may contain two or more types.
[0102] The lactone ring unit is preferably represented by the following general formula (2):
[0103]
[0104] In the general formula (2), R 2 , R 3 and R 4 Each independently represents a hydrogen atom or an organic residue having 1 to 20 carbon atoms. It should be noted that the organic residue may also contain an oxygen atom. The acrylic resin may contain only a single lactone ring unit, or may contain R in the above general formula (2). 2 , R 3 and R 4 Various lactone ring units. Acrylic resins having a lactone ring unit are described in, for example, Japanese Patent Application Laid-Open No. 2008-181078, and the description of the publication is incorporated herein by reference.
[0105] The glutarimide unit is preferably represented by the following general formula (3):
[0106]
[0107] In the general formula (3), R 11 and R 12 Each independently represents hydrogen or an alkyl group having 1 to 8 carbon atoms, and R 13 represents an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an aryl group having 6 to 10 carbon atoms. In the general formula (3), preferably, R 11 and R 12 are independently hydrogen or methyl, R 13 is hydrogen, methyl, butyl or cyclohexyl. More preferably, R 11 Methyl, R 12 is hydrogen, R 13 The acrylic resin may contain only a single glutarimide unit, or may contain R in the above general formula (3). 11 , R 12 and R 13A plurality of different glutarimide units. Acrylic resins having glutarimide units are described in, for example, Japanese Patent Publication No. 2006-309033, Japanese Patent Publication No. 2006-317560, Japanese Patent Publication No. 2006-328334, Japanese Patent Publication No. 2006-337491, Japanese Patent Publication No. 2006-337492, Japanese Patent Publication No. 2006-337493, and Japanese Patent Publication No. 2006-337569, and the descriptions of these publications are incorporated herein by reference. It should be noted that, with respect to the glutaric anhydride unit, in addition to the glutaric anhydride unit represented by R in the general formula (3), 13 Except that the substituted nitrogen atom is an oxygen atom, the above description about the glutarimide unit is applicable.
[0108] The maleic anhydride unit and the maleimide (N-substituted maleimide) unit have structures identified by their names, and thus specific descriptions thereof are omitted.
[0109] The content of the repeating unit containing a ring structure in the acrylic resin is preferably 1 mol% to 50 mol%, more preferably 10 mol% to 40 mol%, and further preferably 20 mol% to 30 mol%. The acrylic resin contains the repeating unit derived from the above-mentioned (meth)acrylic monomer as a main repeating unit.
[0110] <Epoxy resin>
[0111] As the epoxy resin, an epoxy resin having an aromatic ring is preferably used. By using an epoxy resin having an aromatic ring as the epoxy resin, the adhesion between the iodine transmission inhibition layer and the polarizer can be improved. Furthermore, when the adhesive layer is configured to be adjacent to the iodine transmission inhibition layer, the anchoring force of the adhesive layer can be improved. As the epoxy resin having an aromatic ring, bisphenol-type epoxy resins such as bisphenol A epoxy resin, bisphenol F epoxy resin, and bisphenol S epoxy resin can be cited; phenol novolac epoxy resins, cresol novolac epoxy resins, hydroxybenzaldehyde phenol novolac epoxy resins and other novolac epoxy resins; glycidyl ether of tetrahydroxyphenylmethane, glycidyl ether of tetrahydroxybenzophenone, epoxidized polyethylene phenol and other multifunctional epoxy resins, naphthol epoxy resins, naphthalene epoxy resins, biphenyl epoxy resins, etc. Bisphenol A epoxy resin, biphenyl epoxy resin, and bisphenol F epoxy resin are preferably used. The epoxy resins may be used alone or in combination of two or more.
[0112] The iodine permeation inhibition layer can be formed by applying an organic solvent solution of the resin as described above to form a coating film, and the coating film is solidified or thermally cured to form. As an organic solvent, any appropriate organic solvent that can dissolve or uniformly disperse an acrylic resin can be used. As a specific example of an organic solvent, ethyl acetate, toluene, methyl ethyl ketone (MEK), methyl isobutyl ketone (MIBK), cyclopentanone, and cyclohexanone can be cited. The resin concentration of the solution is preferably 3 to 20 parts by weight relative to 100 parts by weight of the solvent. As long as it is such a resin concentration, a uniform coating film can be formed.
[0113] The solution can be applied to any appropriate substrate, or to a polarizer. When the solution is applied to the substrate, the solidified product (iodine permeation inhibition layer) of the coating film formed on the substrate is transferred to the polarizer. When the solution is applied to the polarizer, a protective layer is directly formed on the polarizer by drying (solidifying) the coating film. Preferably, the solution is applied to the polarizer to form a protective layer directly on the polarizer. As long as it is such a structure, the adhesive layer or adhesive layer required for transfer can be omitted, so the polarizer can be made thinner. As a method for applying the solution, any appropriate method can be adopted. As specific examples, roller coating, spin coating, wire rod coating, dip coating, die coating, curtain coating, spray coating, and blade coating (comma coating, etc.) can be cited.
[0114] The iodine transmission inhibition layer can be formed by solidifying or thermally curing the coating film of the solution. The heating temperature for solidification or thermal curing is preferably 100° C. or less, more preferably 50° C. to 70° C. As long as the heating temperature is within such a range, adverse effects on the polarizer can be prevented. The heating time can be varied according to the heating temperature. The heating time can be, for example, 1 minute to 10 minutes.
[0115] The iodine transmission inhibition layer (substantially an organic solvent solution of the above-mentioned resin) may contain any appropriate additives according to the purpose. Specific examples of additives include ultraviolet absorbers; leveling agents; antioxidants of hindered phenol, phosphorus, sulfur, etc.; stabilizers such as light stabilizers, weather stabilizers, and heat stabilizers; reinforcing materials such as glass fiber and carbon fiber; near-infrared absorbers; flame retardants such as tris(dibromopropyl)phosphate, triallyl phosphate, and antimony oxide; antistatic agents such as anionic, cationic, and nonionic surfactants; colorants such as inorganic pigments, organic pigments, and dyes; organic fillers or inorganic fillers; resin modifiers; organic fillers, inorganic fillers; plasticizers; lubricants; antistatic agents; flame retardants; etc. The type, quantity, combination, and addition amount of the additives may be appropriately set according to the purpose.
[0116] The iodine absorption index of the iodine penetration inhibition layer is, for example, below 0.015. The iodine absorption index is preferably below 0.012, more preferably below 0.009, further preferably below 0.007, and particularly preferably below 0.005. The smaller the iodine absorption index, the more preferred it is, and ideally it is zero, and its lower limit may be, for example, 0.001. The iodine absorption index is an index of the iodine penetration inhibition ability of the iodine penetration inhibition layer, and the smaller the index, the more difficult it is for iodine to be absorbed by the iodine penetration inhibition layer (i.e., iodine is easily blocked by the iodine penetration inhibition layer). Therefore, as long as the iodine absorption index is within such a range, the iodine in the polarizer can be significantly inhibited from moving to the image display device (substantially the image display unit). As a result, when the polarizing plate is applied to the image display device, the resistance value of the electrode can be suppressed from changing under a high temperature and high humidity environment, and the thin polarizing plate can achieve excellent durability under a high temperature and high humidity environment. Furthermore, even when the polarizing plate is applied to an image display device, the corrosion of the metal components (such as electrodes, sensors, wiring, and metal layers) of the image display device can still be significantly suppressed, and the reliability reduction caused by iodine under a high temperature and high humidity environment can be suppressed, so the reflectivity can be suppressed. Furthermore, as described above, the iodine transmission inhibition layer has a potassium absorption index of preferably less than 0.015. The potassium absorption index is more preferably less than 0.013, further preferably less than 0.011, and particularly preferably less than 0.009. The smaller the potassium absorption index, the more preferred it is, and it is ideally zero, and its lower limit can be, for example, 0.002. The potassium absorption index is an index of the potassium transmission inhibition ability of the iodine transmission inhibition layer. The smaller the index, the less potassium is absorbed by the iodine transmission inhibition layer. As a result, the iodine and polypotassium iodide (I3 - K + ) is less likely to be absorbed by the iodine transmission inhibition layer. Therefore, as long as the potassium absorption index is within such a range, the movement of iodine can be suppressed not only in the form of elemental iodine but also in the form of potassium iodide and polypotassium iodide. The iodine absorption index can be defined as the iodine intensity (kcps) obtained by X-ray fluorescence analysis of the iodine transmission inhibition layer, and the potassium absorption index can be defined as the potassium intensity (kcps) obtained by X-ray fluorescence analysis of the iodine transmission inhibition layer.
[0117] B. Polarizing plate with phase difference layer
[0118] B-1. Overall structure of polarizing plate with phase difference layer
[0119] The polarizing plate with a phase difference layer in an embodiment of the present invention has a polarizing plate and a phase difference layer. The polarizing plate is the polarizing plate described in the above-mentioned item A. In an embodiment of the present invention, the phase difference layer is arranged between the polarizer and the adhesive layer. The phase difference layer is an orientation solidified layer of a liquid crystal compound having a circular polarization function or an elliptically polarizing function (hereinafter sometimes referred to as a liquid crystal orientation solidified layer). Figure 2A A schematic cross-sectional view of a polarizing plate with a phase difference layer according to one embodiment of the present invention; Figure 2BThis is a schematic cross-sectional view of a polarizing plate with a retardation layer according to another embodiment of the present invention. Figure 2A and Figure 2B The polarizing plates 100 and 101 with phase difference layers each have a protective layer 12, a polarizer 11, a phase difference layer 20 and an adhesive layer 30 in order from the visual recognition side. In an embodiment of the present invention, an iodine transmission inhibition layer 40 is disposed between the polarizer 11 and the adhesive layer 30. By providing an iodine transmission inhibition layer in the polarizing plate with a phase difference layer, as described above with respect to the polarizing plate, the movement of iodine in the polarizer to the adhesive layer (ultimately an image display device, in essence an image display unit) can be significantly suppressed. As a result, the ITO resistance value increase rate of the polarizing plate with a phase difference layer can be set to less than 100%. Therefore, when the polarizing plate with a phase difference layer is applied to an image display device, the resistance value change of the electrode in a high temperature and high humidity environment can be suppressed, and the thin polarizing plate with a phase difference layer can achieve excellent durability in a high temperature and high humidity environment. Furthermore, when the polarizing plate with a phase difference layer is applied to an image display device, the corrosion of metal components (such as electrodes, sensors, wiring, and metal layers) of the image display device can be significantly suppressed, and the increase in reflectivity under a high temperature and high humidity environment can be suppressed. Figure 2A As shown, it is disposed between the polarizer 11 and the phase difference layer 20 (i.e., adjacent to the polarizer 11), and can also be as shown Figure 2B As shown, it is arranged between the phase difference layer 20 and the adhesive layer 30. When the iodine transmission inhibition layer is arranged between the polarizer and the phase difference layer (especially when the iodine transmission inhibition layer is adjacent to the polarizer), the migration of iodine from the polarizer under high temperature and high humidity environment can be suppressed, which has the advantage of improved reliability. When the iodine transmission inhibition layer is arranged between the phase difference layer and the adhesive layer (especially when the iodine transmission inhibition layer is adjacent to the adhesive layer), components other than iodine that may affect metal corrosion (such as residual monomer components in ultraviolet curing adhesives and decomposition products of photoinitiators) can also be prevented from migrating into the adhesive, which has the advantage of further improving the metal corrosion inhibition effect.
[0120] like Figure 3As shown, in another embodiment of the polarizing plate 102 with a phase difference layer, another phase difference layer 50 and / or a conductive layer or an isotropic substrate 60 with a conductive layer may also be provided. The other phase difference layer 50 is typically provided between the phase difference 20 and the adhesive layer 30 (i.e., the outside of the phase difference layer 20). The other phase difference layer is typically provided with a refractive index characteristic showing a relationship of nz>nx=ny. The conductive layer or the isotropic substrate 60 with a conductive layer is typically provided between the iodine transmission inhibition layer 40 and the adhesive layer 30 (i.e., the outside of the iodine transmission inhibition layer 40). The other phase difference layer 50 and the conductive layer or the isotropic substrate 60 with a conductive layer are typically provided in sequence starting from the phase difference layer 20 side. In the example shown in the figure, an iodine transmission suppression layer 40, a phase difference layer 20, another phase difference layer 50, and an isotropic substrate 60 with a conductive layer are sequentially arranged from the visual recognition side. As long as the other phase difference layer 50 is arranged between the phase difference 20 and the adhesive layer 30, and the conductive layer or the isotropic substrate 60 with a conductive layer is arranged between the iodine transmission suppression layer 40 and the adhesive layer 30, any appropriate configuration order can be adopted. The other phase difference layer 50 and the conductive layer or the isotropic substrate 60 with a conductive layer are representatively any layers arranged as needed, and either or both can be omitted. It should be noted that, for convenience, the phase difference layer 20 is sometimes referred to as the first phase difference layer, and the other phase difference layer 50 is referred to as the second phase difference layer. When a conductive layer or an isotropic substrate with a conductive layer is provided, the polarizing plate with a phase difference layer can be applied to a so-called embedded touch panel type input display device in which a touch sensor is incorporated between an image display unit (such as an organic EL unit) and a polarizing plate. In the embodiment of the present invention, by providing the conductive layer or the isotropic substrate 60 with a conductive layer on the outer side of the iodine permeation suppression layer 40, the corrosion of the conductive layer can be significantly suppressed.
[0121] As described above, the first phase difference layer 20 is a liquid crystal alignment solidification layer. The first phase difference layer 20 may be Figure 2A , Figure 2B and Figure 3 The single layer shown may also have Figure 4 The stacked structure of the first liquid crystal alignment fixed layer 21 and the second liquid crystal alignment fixed layer 22 is shown.
[0122] The above embodiments may be appropriately combined, and changes that are obvious in the industry may be added to the components of the above embodiments. Figure 2B The polarizing plate 101 with a phase difference layer is provided with a second phase difference layer 50 and / or a conductive layer or an isotropic substrate 60 with a conductive layer; Figure 2B The phase difference layer 20 of the polarizing plate 101 with a phase difference layer may also have the following Figure 4 2-layer structure; can be used Figure 4The polarizing plate 103 with a phase difference layer is provided with a second phase difference layer 50 and / or a conductive layer or an isotropic substrate 60 with a conductive layer; Figure 3 The iodine transmission suppression layer 40 of the polarizing plate 102 with a retardation layer may be disposed between the retardation layer 20 and the conductive layer or the isotropic substrate 60 with a conductive layer.
[0123] The polarizing plate with a phase difference layer according to the embodiment of the present invention may further include other phase difference layers. The optical properties (such as refractive index properties, in-plane phase difference, Nz coefficient, photoelastic coefficient), thickness, configuration position, etc. of other phase difference layers can be appropriately set according to the purpose.
[0124] The total thickness of the polarizing plate with a phase difference layer is preferably less than 60 μm, more preferably less than 55 μm, further preferably less than 50 μm, and particularly preferably less than 40 μm. The lower limit of the total thickness may be, for example, 28 μm. According to an embodiment of the present invention, such an extremely thin polarizing plate with a phase difference layer can be realized, and further, such an extremely thin polarizing plate with a phase difference layer can achieve excellent durability in a high temperature and high humidity environment. Furthermore, even when such a very thin polarizing plate with a phase difference layer is applied to an image display device, the corrosion of metal components (such as electrodes, sensors, wiring, and metal layers) of the image display device can still be significantly suppressed, and the increase in reflectivity in a high temperature and high humidity environment can be suppressed. It should be noted that the so-called total thickness of the polarizing plate with a phase difference layer refers to the total thickness of the polarizing plate, the phase difference layer (the first phase difference layer and the second phase difference layer when the second phase difference layer exists), the iodine transmission inhibition layer, and the adhesive layer or adhesive layer used to stack them (that is, the total thickness of the polarizing plate with a phase difference layer does not include the thickness of the conductive layer or the isotropic substrate 60 with a conductive layer, the adhesive layer 30, and the peeling film that can be temporarily bonded to its surface).
[0125] The above-mentioned records of item A regarding the composition, effect and use of the polarizing plate that can also be applied to the polarizing plate with a phase difference layer can be cited as the records of the polarizing plate with a phase difference layer. For example, the records regarding the increase rate of ITO resistance value, the shape (single sheet or long strip) and thinning of the polarizing plate, the image display device to which the polarizing plate can be applied, the peeling film, and the direct formation of an iodine transmission inhibition layer on the polarizer can be cited as the records of the polarizing plate with a phase difference layer. These are illustrative and the records that can be cited are not limited to these, which is self-evident. Similarly, the records described later regarding the composition, effect and use of the polarizing plate with a phase difference layer that can be cited in the polarizing plate can be cited as the records of the polarizing plate.
[0126] The first phase difference layer, the second phase difference layer, and the conductive layer or the isotropic substrate with a conductive layer as components of the polarizing plate with a phase difference layer are described below. The polarizer, the protective layer, and the iodine transmission suppression layer are as described in the above section A.
[0127] B-2. First phase difference layer
[0128] The first phase difference layer 20 is a liquid crystal orientation solidification layer as described above. By using a liquid crystal compound, the difference between nx and ny of the obtained phase difference layer can be significantly larger than that of a non-liquid crystal material, so the thickness of the phase difference layer used to obtain the desired in-plane phase difference can be significantly smaller. As a result, further thinning of the polarizing plate with a phase difference layer can be achieved. In this specification, the so-called "liquid crystal orientation solidification layer" refers to a layer in which the liquid crystal compound is oriented in a prescribed direction within the layer and its orientation state is fixed. It should be noted that the "orientation solidification layer" is a concept of an orientation solidification layer obtained by solidifying a liquid crystal monomer as described later. In the present embodiment, a representative state is that the rod-shaped liquid crystal compound is oriented (parallel orientation) in a state arranged along the slow axis direction of the first phase difference layer.
[0129] As the liquid crystal compound, for example, a liquid crystal compound whose liquid crystal phase is a nematic phase (nematic liquid crystal) can be cited. As such a liquid crystal compound, for example, a liquid crystal polymer or a liquid crystal monomer can be used. The liquid crystal property of the liquid crystal compound can be expressed by a lyotropic or thermotropic mechanism. The liquid crystal polymer and the liquid crystal monomer can be used alone or in combination.
[0130] When the liquid crystal compound is a liquid crystal monomer, the liquid crystal monomer is preferably a polymerizable monomer and a cross-linkable monomer. This is because the orientation state of the liquid crystal monomer can be fixed by polymerizing or cross-linking (i.e. curing) the liquid crystal monomer. After the liquid crystal monomer is oriented, for example, when the liquid crystal monomers are polymerized or cross-linked with each other, the above-mentioned orientation state can be fixed. Here, the polymer is formed by polymerization, and the three-dimensional network structure is formed by cross-linking, but these are non-liquid crystal. Therefore, the first phase difference layer formed, for example, will not change into a liquid crystal phase, a glass phase, or a crystalline phase due to temperature changes, which is unique to liquid crystal compounds. As a result, the first phase difference layer becomes a phase difference layer that is not affected by temperature changes and has extremely excellent stability.
[0131] The temperature range in which the liquid crystal monomer exhibits liquid crystallinity varies depending on the type of the liquid crystal monomer. Specifically, the temperature range is preferably 40°C to 120°C, more preferably 50°C to 100°C, and most preferably 60°C to 90°C.
[0132] As the above-mentioned liquid crystal monomer, any appropriate liquid crystal monomer can be used. For example, the polymerizable liquid crystal original compounds described in Japanese Patent Table 2002-533742 (WO00 / 37585), EP358208 (US5211877), EP66137 (US4388453), WO93 / 22397, EP0261712, DE19504224, DE4408171 and GB2280445 can be used. As a specific example of such a polymerizable liquid crystal original compound, for example, the trade name LC242 of BASF, the trade name E7 of Merck, and the trade name LC-Sillicon-CC3767 of Wacker-Chem can be cited. As a liquid crystal monomer, it is preferably, for example, a nematic liquid crystal monomer.
[0133] The liquid crystal orientation solidification layer can be formed as follows: an orientation treatment is applied to the surface of a predetermined substrate, and a coating liquid containing a liquid crystal compound is applied to the surface to orient the liquid crystal compound in a direction corresponding to the orientation treatment, and the orientation state is fixed, thereby forming. In one embodiment, the substrate is any appropriate resin film, and the liquid crystal orientation solidification layer formed on the substrate can be transferred to the surface of an adjacent layer (e.g., a polarizer, an iodine transmission inhibition layer).
[0134] As the above-mentioned orientation treatment, any appropriate orientation treatment can be adopted. Specifically, mechanical orientation treatment, physical orientation treatment, and chemical orientation treatment can be cited. As specific examples of mechanical orientation treatment, friction treatment and stretching treatment can be cited. As specific examples of physical orientation treatment, magnetic field orientation treatment and electric field orientation treatment can be cited. As specific examples of chemical orientation treatment, oblique evaporation method and optical orientation treatment can be cited. The processing conditions of various orientation treatments can adopt any appropriate conditions according to the purpose.
[0135] The liquid crystal compound can be aligned by treating it at a temperature that exhibits a liquid crystal phase depending on the type of the liquid crystal compound. By such a temperature treatment, the liquid crystal compound changes to a liquid crystal state, and the liquid crystal compound is aligned in the alignment treatment direction of the substrate surface.
[0136] In one embodiment, the alignment state is fixed by cooling the aligned liquid crystal compound. When the liquid crystal compound is a polymerizable monomer or a crosslinkable monomer, the alignment state is fixed by subjecting the aligned liquid crystal compound to a polymerization treatment or a crosslinking treatment.
[0137] Specific examples of the liquid crystal compound and details of the method for forming the aligned solid layer are described in Japanese Unexamined Patent Application Publication No. 2006-163343, and the contents of this publication are incorporated herein by reference.
[0138] In one embodiment, the first retardation layer 20 is a single layer as shown in Figure 2A , Figure 2B and Figure 3 . When the first retardation layer 20 is composed of a single layer, its thickness is preferably 0.5 μm to 7 μm, more preferably 1 μm to 5 μm. By using a liquid crystal compound, an in-plane retardation equivalent to that of a resin film can be achieved at a thickness significantly thinner than that of the resin film.
[0139] The first retardation layer has a circular polarization function or an elliptical polarization function as described above. Typically, the refractive index characteristics of the first retardation layer show a relationship of nx > ny = nz. Typically, the first retardation layer is provided to impart antireflection characteristics to the polarizing plate. When the first retardation layer is a single layer, it can function as a λ / 4 plate. At this time, the in-plane retardation Re(550) of the first retardation layer is preferably 100 nm to 190 nm, more preferably 110 nm to 170 nm, and further preferably 130 nm to 160 nm. It should be noted that here, "ny = nz" includes not only the case where ny and nz are exactly equal but also the case where they are substantially equal. Therefore, there may be cases where ny > nz or ny < nz within the scope that does not impair the effects of the present invention.
[0140] The Nz coefficient of the first retardation layer is preferably 0.9 to 1.5, more preferably 0.9 to 1.3. By satisfying such a relationship, when the polarizing plate with the retardation layer is used in an image display device, a very excellent reflected hue can be achieved.
[0141] The first retardation layer can exhibit an anomalous dispersion wavelength characteristic in which the retardation value increases with the wavelength of the measurement light, a normal wavelength dispersion characteristic in which the retardation value decreases with the wavelength of the measurement light, or a flat wavelength dispersion characteristic in which the retardation value hardly changes with the wavelength of the measurement light. In one embodiment, the first retardation layer exhibits an anomalous dispersion wavelength characteristic. At this time, Re(450) / Re(550) of the retardation layer is preferably 0.8 or more and less than 1, more preferably 0.8 or more and 0.95 or less. With such a configuration, very excellent antireflection characteristics can be achieved.
[0142] The angle θ formed by the slow axis of the first retardation layer 20 and the absorption axis of the polarizing member 11 is preferably 40° to 50°, more preferably 42° to 48°, and further preferably about 45°. As long as the angle θ is within such a range, by forming the first retardation layer into a λ / 4 plate as described above, a polarizing plate with a retardation layer having very excellent circular polarization characteristics (resulting in very excellent antireflection characteristics) can be obtained.
[0143] In another embodiment, the first retardation layer 20 is as shown in Figure 4As shown, it has a stacked structure of a first liquid crystal orientation solidification layer 21 and a second liquid crystal orientation solidification layer 22. At this time, either the first liquid crystal orientation solidification layer 21 or the second liquid crystal orientation solidification layer 22 can function as a λ / 4 plate, and the other can function as a λ / 2 plate. Therefore, the thickness of the first liquid crystal orientation solidification layer 21 and the second liquid crystal orientation solidification layer 22 can be adjusted in a manner to obtain the desired in-plane phase difference of the λ / 4 plate or the λ / 2 plate. For example, when the first liquid crystal orientation solidification layer 21 functions as a λ / 2 plate and the second liquid crystal orientation solidification layer 22 functions as a λ / 4 plate, the thickness of the first liquid crystal orientation solidification layer 21 is, for example, 2.0 μm to 3.0 μm, and the thickness of the second liquid crystal orientation solidification layer 22 is, for example, 1.0 μm to 2.0 μm. At this time, the in-plane phase difference Re (550) of the first liquid crystal orientation solidification layer is preferably 200nm to 300nm, more preferably 230nm to 290nm, and further preferably 250nm to 280nm. The in-plane phase difference Re (550) of the second liquid crystal orientation solidification layer is as described above for a single layer. The angle formed by the slow axis of the first liquid crystal orientation solidification layer and the absorption axis of the polarizer is preferably 10° to 20°, more preferably 12° to 18°, and further preferably about 15°. The angle formed by the slow axis of the second liquid crystal orientation solidification layer and the absorption axis of the polarizer is preferably 70° to 80°, more preferably 72° to 78°, and further preferably about 75°. As long as it is such a structure, characteristics close to the ideal abnormal wavelength dispersion characteristics can be obtained, and as a result, very excellent anti-reflection characteristics can be achieved. Regarding the liquid crystal compounds constituting the first liquid crystal orientation solidification layer and the second liquid crystal orientation solidification layer, the formation method of the first liquid crystal orientation solidification layer and the second liquid crystal orientation solidification layer, the optical characteristics, etc., as described above for a single layer.
[0144] B-3. Second phase difference layer
[0145] As described above, the second phase difference layer can be a so-called positive C-plate whose refractive index characteristics show the relationship of nz>nx=ny. By using a positive C-plate as the second phase difference layer, oblique reflection can be well prevented, and the anti-reflection function can be made wide-viewing angle. At this time, the phase difference Rth(550) in the thickness direction of the second phase difference layer is preferably -50nm~-300nm, more preferably -70nm~-250nm, further preferably -90nm~-200nm, and particularly preferably -100nm~-180nm. Here, "nx=ny" not only includes the case where nx and ny are strictly equal, but also includes the case where nx and ny are substantially equal. That is, the in-plane phase difference Re(550) of the second phase difference layer can be less than 10nm.
[0146] The second phase difference layer having a refractive index characteristic of nz>nx=ny can be formed by any appropriate material. The second phase difference layer is preferably formed by a thin film containing a liquid crystal material fixed in a homeotropic orientation. The liquid crystal material (liquid crystal compound) that can be homeotropically oriented can be a liquid crystal monomer or a liquid crystal polymer. As a specific example of the liquid crystal compound and the method for forming the phase difference layer, the liquid crystal compound and the method for forming the phase difference layer described in paragraphs
[0020] to
[0028] of Japanese Patent Gazette No. 2002-333642 can be cited. At this time, the thickness of the second phase difference layer is preferably 0.5μm to 10μm, more preferably 0.5μm to 8μm, and further preferably 0.5μm to 5μm.
[0147] B-4. Conductive layer or isotropic substrate with conductive layer
[0148] The conductive layer can be formed by forming a metal oxide film on any appropriate substrate using any appropriate film forming method (e.g., vacuum evaporation, sputtering, CVD, ion plating, spraying, etc.). Examples of the metal oxide include indium oxide, tin oxide, zinc oxide, indium tin composite oxide, tin antimony composite oxide, zinc aluminum composite oxide, and indium zinc composite oxide. Among them, indium tin composite oxide (ITO) is preferred.
[0149] When the conductive layer contains a metal oxide, the thickness of the conductive layer is preferably 50 nm or less, more preferably 35 nm or less. The lower limit of the thickness of the conductive layer is preferably 10 nm.
[0150] The conductive layer can be transferred from the substrate to the first phase difference layer (or, the iodine transmission inhibition layer or the second phase difference layer when the second phase difference layer exists) and the conductive layer itself can be used as a constituent layer of the polarizing plate with a phase difference layer, or it can be laminated on the first phase difference layer (or, the iodine transmission inhibition layer or the second phase difference layer when the second phase difference layer exists) in the form of a laminate with the substrate (substrate with a conductive layer). Preferably, the substrate is optically isotropic, and therefore, the conductive layer can be used as an isotropic substrate with a conductive layer for a polarizing plate with a phase difference layer.
[0151] As an optically isotropic substrate (isotropic substrate), any appropriate isotropic substrate can be used. As the material constituting the isotropic substrate, for example, a material having a resin without a conjugated system such as norbornene resin or olefin resin as the main skeleton, a material having a cyclic structure such as a lactone ring or a glutarimide ring in the main chain of an acrylic resin, etc. can be cited. If such a material is used, the phase difference caused by the orientation of the molecular chain can be suppressed to be smaller when forming the isotropic substrate. The thickness of the isotropic substrate is preferably less than 50 μm, more preferably less than 35 μm. The lower limit of the thickness of the isotropic substrate is, for example, 20 μm.
[0152] The conductive layer and / or the conductive layer of the isotropic substrate with a conductive layer can be patterned as needed. Through patterning, a conductive portion and an insulating portion can be formed. As a result, an electrode can be formed. The electrode can function as a touch sensor electrode for sensing contact with the touch panel. As a patterning method, any appropriate method can be used. As specific examples of patterning methods, wet etching and screen printing can be cited.
[0153] C. Image display device
[0154] The polarizing plate described in item A above and the polarizing plate with a phase difference layer described in item B above can be applied to an image display device. Therefore, an embodiment of the present invention includes an image display device using such a polarizing plate or a polarizing plate with a phase difference layer. As a representative example of an image display device, a liquid crystal display device and an electroluminescent (EL) display device (such as an organic EL display device and an inorganic EL display device) can be cited. The image display device of an embodiment of the present invention is representatively provided with a polarizing plate described in item A above or a polarizing plate with a phase difference layer described in item B above on its visual recognition side. The polarizing plate with a phase difference layer is stacked in such a way that the phase difference layer becomes the side of the image display unit (such as a liquid crystal unit, an organic EL unit, an inorganic EL unit) (the polarizer becomes the visual recognition side). Although such an image display device is very thin, the corrosion of metal components is significantly suppressed, and the change in the resistance value of the electrode in a high temperature and high humidity environment is suppressed. In one embodiment, the image display device has a curved shape (substantially a curved display screen) and / or is bendable or foldable. It should be noted that the polarizing plate described in the above section A may be disposed on the back side of the image display device according to the purpose.
[0155] Example
[0156] The present invention is described in detail below using examples, but the present invention is not limited to these examples. The measuring methods of each characteristic are as follows. In addition, unless otherwise specified, the "parts" and "%" in the examples and comparative examples are weight references.
[0157] (1) Thickness
[0158] The thickness of 10 μm or less was measured using an interferometer thickness meter (manufactured by Otsuka Electronics Co., Ltd., product name "MCPD-3000"), and the thickness of more than 10 μm was measured using a digital micrometer (manufactured by Anritsu Corporation, product name "KC-351C").
[0159] (2) Iodine Presence Index
[0160] The polarizing plate or polarizing plate with a phase difference layer obtained in the embodiment and the comparative example is bonded to the alkali-free glass to prepare a test sample. After the test sample is subjected to a reliability test (placed in an environment of 85°C 85% RH for 240 hours, and then placed in an environment of 23°C 55% RH for 24 hours), it is peeled off from the alkali-free glass together with the adhesive with a trimming knife. The adhesive surface of the peeled test sample is measured by secondary ion mass spectrometry (TOF-SIMS) using "TOFSIMS5" manufactured by IONTOF. The measurement conditions are as follows.
[0161] ·Irradiated primary ions: Bi3 2+
[0162] Primary ion acceleration voltage: 25kV
[0163] ·Measurement area: 100μm 2
[0164] Determination of polarity: negative ions
[0165] From the obtained negative secondary ions, C3H3O2 derived from acrylic acid (adhesive) is selected. - The ion intensity of (m / z=71) and I derived from iodine - The ion intensity of (m / z=127) was used to calculate the iodine presence index using the following formula.
[0166] Iodine presence index = I - Ionic strength / C3H3O2 - Ionic Strength
[0167] (3) Iodine absorption index and potassium absorption index
[0168] The resin solution used in the examples and comparative examples was coated on a 38 μm polyethylene terephthalate (PET) film in such a manner that the thickness after drying became 1 μm and dried to obtain a test sample of the resin layer / PET film. The obtained test sample was immersed in a 10% aqueous solution of potassium iodide (90 parts by weight of pure water, 10 parts by weight of potassium iodide) adjusted to 23°C for 24 hours. After immersion, the test sample was taken out from the aqueous solution, and after wiping off the water droplets on the surface, the intensity of iodine and potassium (kcps) was obtained by fluorescent X-ray measurement of the surface of the resin layer. The intensity of iodine obtained was used as the iodine absorption index, and the intensity of potassium was used as the potassium absorption index. It should be noted that the conditions for fluorescent X-ray analysis are as follows.
[0169] Analyzer: X-ray fluorescence analyzer (XRF), manufactured by Rigaku Corporation, product name "ZSX100e"
[0170] Test specimen: round specimen with a diameter of 10 mm
[0171] ·Cathode: Rhodium
[0172] Spectroscopic crystal: lithium fluoride
[0173] Excitation light energy: 40kV-90mA
[0174] ·Iodine determination radiation: I-LA
[0175] Quantitative method: FP method
[0176] 2θ angle peak: 103.078deg (iodine), 136.847deg (potassium)
[0177] ·Measurement time: 40 seconds
[0178] (4) ITO resistance value increase rate
[0179] By sputtering, an amorphous ITO layer (thickness 20nm) was formed on an alkali-free glass ("EG-XG" manufactured by Corning, thickness 0.7mm), and a laminate (ITO glass) of ITO layer / alkali-free glass was prepared. The Sn content in the ITO constituting the ITO layer was 3 wt%. The Sn content was calculated from the weight of Sn atoms in ITO / (weight of Sn atoms + weight of In atoms). The resistance value of the ITO layer surface of the obtained ITO glass was measured by a 4-terminal method (manufactured by ACCENT, product name "HL5500PC") as the initial resistance value.
[0180] Next, the polarizing plate or polarizing plate with a phase difference layer obtained in the embodiment and the comparative example is attached to the surface of the ITO layer of the ITO glass as a test sample. After the test sample is subjected to a reliability test (240 hours under an environment of 60°C and 95% RH), the polarizing plate or polarizing plate with a phase difference layer is peeled off from the ITO glass, and the resistance value of the ITO layer surface is measured in the same manner as above. The ITO resistance value increase rate is calculated by the following formula.
[0181] Resistance increase rate (%) = {(resistance after reliability test - initial resistance) / (initial resistance)} × 100
[0182] Furthermore, evaluation was performed based on the following criteria.
[0183] Good: Resistance value increase rate is less than 100%
[0184] Bad: Resistance value increase rate is greater than 100%
[0185] (5) Change in polarization
[0186] The polarizing plate or polarizing plate with a phase difference layer obtained in the embodiment and the comparative example is bonded to an alkali-free glass as a test sample. The polarization degree of the test sample is measured by a conventional method and is taken as the initial polarization degree. Furthermore, after the test sample is subjected to a reliability test (placed in an environment of 85°C·85% RH for 240 hours, and then placed in an environment of 23°C·55% RH for 24 hours), the polarization degree is measured in the same manner as above. The change in polarization degree is calculated by the following formula.
[0187] Polarization change (%) = initial polarization (%) - polarization after reliability test (%)
[0188] Furthermore, evaluation was performed based on the following criteria.
[0189] Good: Polarization change less than 5.0%
[0190] Defective: Polarization change is 5.0% or more
[0191] (6) Increased reflectivity
[0192] The polarizing plate with a phase difference layer obtained in the embodiment and the comparative example is bonded to an alkali-free glass as a test sample. The test sample is placed on a reflective plate with a reflectivity of 80%, and the value at 550nm using a spectrophotometer (CM700D manufactured by Konica Minolta) in SCI mode is taken as the reflectivity (%), which is taken as the initial reflectivity. Furthermore, after the test sample is subjected to a reliability test (placed in an environment of 60°C·90%RH for 500 hours, and then placed in an environment of 23°C·55%RH for 24 hours), the reflectivity is measured in the same manner as above. The reflectivity rise is calculated by the following formula.
[0193] Reflectivity increase (%) = initial reflectivity (%) - reflectivity after reliability test (%)
[0194] Furthermore, evaluation was performed based on the following criteria.
[0195] Good: reflectivity increase is less than 0.50%
[0196] Allowable: Reflectivity increase is 0.50% or more and less than 1.00%
[0197] Defective: Reflectivity rises to 1.00% or more
[0198] (7) Metal corrosion (48 hours)
[0199] A silver nanowire liquid (manufactured by MERCK, nanowire size: diameter 115 nm, length 20 μm to 50 μm, isopropyl alcohol (IPA) solution of 0.5% solid content) was applied to one side of a 50 μm polyethylene terephthalate (PET) film using a wire rod so that the wet film thickness was 15 μm, and then dried in an oven at 100° C. for 5 minutes to form a silver nanowire coating film. Next, an overcoating liquid (solid content concentration: about 1%) containing 99 parts of methyl isobutyl ketone (MIBK), 1 part of pentaerythritol tetraacrylate (PETA) and 0.03 parts of a photopolymerization initiator (manufactured by BASF, product name “IRGACURE 907”) was applied to the surface of the silver nanowire coating film using a wire rod so that the wet film thickness was 10 μm, and then dried in an oven at 100° C. for 5 minutes. Next, the outer coating film was cured by irradiating active energy rays to prepare a metal thin film having a structure of PET film / silver nanowire layer / outer coating layer (thickness 100 nm). The metal thin film was bonded to a glass plate with a thickness of 0.5 mm using an adhesive (15 μm) to obtain a laminate of metal thin film / adhesive / glass plate. The resistance value of the obtained laminate was measured with a non-contact resistance measuring instrument (manufactured by Napson, product name "EC-80"), and the result was 50Ω / □.
[0200] The polarizing plate or polarizing plate with a phase difference layer obtained in the embodiment and the comparative example is attached to the outer coating surface of the metal film of the laminate as a test sample. The resistance value of the test sample is measured by a non-contact resistance measuring instrument as the initial resistance value. Furthermore, after the test sample is subjected to a reliability test (placed in an environment of 85°C·85%RH for 48 hours, and then placed in an environment of 23°C·55%RH for 2 hours), the resistance value is measured in the same manner as above. The resistance value increase rate is calculated by the following formula. It should be noted that when the measured value (resistance value) is greater than the measurement limit (1000Ω / □) of the non-contact resistance measuring instrument, the measured value is assumed to be 1500Ω / □.
[0201] Resistance value increase rate (%) = {(resistance value after reliability test - initial resistance value) / initial resistance value} × 100
[0202] Furthermore, evaluation was performed based on the following criteria.
[0203] Good: Resistance value increase rate is less than 200%
[0204] Defective: Resistance value increase rate is more than 200%
[0205] (8) Metal corrosion (200 hours)
[0206] The polarizing plate with a phase difference layer obtained in the embodiment and the comparative example is bonded to the outer coating-forming surface of the metal film of the laminate obtained in (2) as a test sample. The resistance value of the test sample is measured by a non-contact resistance meter as the initial resistance value. Furthermore, after the test sample is subjected to a reliability test (placed in an environment of 85°C·85%RH for 200 hours, and then placed in an environment of 23°C·55%RH for 2 hours), the resistance value is measured in the same manner as above. The resistance value increase rate is calculated by the following formula. It should be noted that when the measured value (resistance value) is greater than the measurement limit (1000Ω / □) of the non-contact resistance meter, the measured value is assumed to be 1500Ω / □.
[0207] Resistance value increase rate (%) = {(resistance value after reliability test - initial resistance value) / initial resistance value} × 100
[0208] Furthermore, evaluation was performed based on the following criteria.
[0209] Excellent: Resistance value increase rate is less than 200%
[0210] Good: The resistance value increase rate is 200% or more and less than 2000%
[0211] Defective: Resistance value increase rate is more than 2000%
[0212] [Example 1]
[0213] 1. Production of polarizer
[0214] As the thermoplastic resin substrate, a long amorphous polyethylene terephthalate copolymer film (thickness: 100 μm) having a water absorption of 0.75% and a Tg of about 75° C. was used. One surface of the resin substrate was subjected to a corona treatment.
[0215] 13 parts by weight of potassium iodide was added to 100 parts by weight of a PVA-based resin prepared by mixing polyvinyl alcohol (degree of polymerization 4200, degree of saponification 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., trade name "GOHSEFIMER Z410") in a ratio of 9:1, and the resulting product was dissolved in water to prepare a PVA aqueous solution (coating solution).
[0216] The PVA aqueous solution was applied to the corona-treated surface of the resin substrate and dried at 60° C. to form a 13 μm-thick PVA-based resin layer, thereby producing a laminate.
[0217] The obtained laminate was subjected to free-end uniaxial stretching to 2.4 times in the longitudinal direction (longitudinal direction) between rolls having different peripheral speeds in an oven at 130° C. (in-air auxiliary stretching treatment).
[0218] Next, the laminate was immersed in an insolubilization bath (boric acid aqueous solution prepared by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (insolubilization treatment).
[0219] Next, the polarizer was immersed in a dyeing bath (an iodine aqueous solution obtained by mixing iodine and potassium iodide in a weight ratio of 1:7 to 100 parts by weight of water) at a liquid temperature of 30°C for 60 seconds (dyeing treatment) while adjusting the concentration so that the single body transmittance (Ts) of the final polarizer would be 43.0% or more.
[0220] Next, the film was immersed in a crosslinking bath (boric acid aqueous solution prepared by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (crosslinking treatment).
[0221] Thereafter, the laminate was immersed in an aqueous boric acid solution (boric acid concentration of 4.0 wt %, potassium iodide concentration of 5 wt %) at a liquid temperature of 70°C and uniaxially stretched (underwater stretching treatment) in the longitudinal direction (length direction) between rollers with different peripheral speeds so that the total stretching ratio became 5.5 times.
[0222] Thereafter, the laminate was immersed in a cleaning bath (an aqueous solution prepared by mixing 4 parts by weight of potassium iodide with respect to 100 parts by weight of water) at a liquid temperature of 20° C. (cleaning treatment).
[0223] Thereafter, the laminate was brought into contact with a SUS heating roll having a surface temperature of 75° C. for about 2 seconds while being dried in an oven maintained at 90° C. (drying shrinkage treatment). The shrinkage rate of the laminate in the width direction due to the drying shrinkage treatment was 5.2%.
[0224] In this manner, a polarizer having a thickness of 5 μm was formed on the resin substrate.
[0225] 2. Production of polarizing plate
[0226] The surface of the polarizer obtained above (the surface on the opposite side to the resin substrate) is bonded with an HC-COP film as a protective layer by means of an ultraviolet curing adhesive. Specifically, the coating is performed so that the total thickness of the curing adhesive becomes 1.0 μm, and the bonding is performed using a roller mill. Thereafter, UV light is irradiated from the protective layer side to cure the adhesive. It should be noted that the HC-COP film is a film having a hard coating (HC) layer (thickness 2 μm) formed on a cycloolefin (COP) film (manufactured by ZEON Corporation of Japan, product name "ZF12", thickness 25 μm), and the COP film is bonded in such a way that the polarizer side becomes the COP film. Next, the resin substrate is peeled off to obtain a polarizing plate having a structure of a protective layer (HC layer / COP film) / adhesive layer / polarizer.
[0227] 3. Preparation of the First Oriented Solidified Layer and the Second Oriented Solidified Layer Constituting the Phase Difference Layer
[0228] 10 g of a polymerizable liquid crystal showing a nematic liquid crystal phase (manufactured by BASF: trade name "Paliocolor LC242", represented by the following formula) and 3 g of a photopolymerization initiator for the polymerizable liquid crystal compound (manufactured by BASF: trade name "IRGACURE 907") were dissolved in 40 g of toluene to prepare a liquid crystal composition (coating liquid).
[0229]
[0230] The surface of polyethylene terephthalate (PET) film (thickness 38 μm) was rubbed with a rubbing cloth to perform an orientation treatment. The orientation treatment direction was set to be 15° relative to the absorption axis direction of the polarizer when viewed from the visual recognition side when attached to the polarizing plate. The above-mentioned liquid crystal coating liquid was applied to the orientation treatment surface using a rod coater and heated and dried at 90°C for 2 minutes to orient the liquid crystal compound. A metal halide lamp was used at 1 mJ / cm 2 The liquid crystal layer thus formed was irradiated with light to solidify the liquid crystal layer, thereby forming a liquid crystal alignment solidified layer A on the PET film. The liquid crystal alignment solidified layer A had a thickness of 2.5 μm and an in-plane phase difference Re (550) of 270 nm. Furthermore, the liquid crystal alignment solidified layer A had a refractive index distribution of nx>ny=nz.
[0231] The coating thickness was changed, and the orientation treatment direction was set to be 75° relative to the absorption axis direction of the polarizer when viewed from the visual recognition side. The same operation as above was performed to form a liquid crystal orientation solidified layer B on the PET film. The thickness of the liquid crystal orientation solidified layer B was 1.5 μm, and the in-plane phase difference Re (550) was 140 nm. Furthermore, the liquid crystal orientation solidified layer B had a refractive index distribution of nx>ny=nz.
[0232] 4. Formation of phase difference layer
[0233] The liquid crystal orientation solidification layer A and the liquid crystal orientation solidification layer B obtained in the above 3. are transferred in sequence to the surface of the polarizer of the polarizing plate obtained in the above 2. At this time, the transfer (lamination) is performed in a manner that the angle formed by the absorption axis of the polarizer and the slow axis of the liquid crystal orientation solidification layer A is 15° and the angle formed by the absorption axis of the polarizer and the slow axis of the liquid crystal orientation solidification layer B is 75°. It should be noted that each transfer (lamination) is performed with the aid of the ultraviolet curing adhesive (thickness 1.0 μm) used in the above 2. In this way, a laminate having the structure of protective layer (HC layer / COP film) / adhesive layer / polarizer / adhesive layer / phase difference layer (first liquid crystal orientation solidification layer / adhesive layer / second liquid crystal orientation solidification layer) is prepared.
[0234] 5. Preparation of polarizing plate with phase difference layer
[0235] 20 parts of acrylic resin (manufactured by Kusumoto Chemicals Co., Ltd., product name "B-811", Tg: 110°C, Mw: 40000) were dissolved in 80 parts of methyl ethyl ketone to obtain a resin solution (20%). The resin solution was applied to the surface of the second liquid crystal orientation solidified layer of the laminate obtained in 4. above using a wire rod, and the coated film was dried at 60°C for 5 minutes to form an iodine transmission inhibition layer (thickness 0.5 μm) in the form of a solidified product of the coated film of the organic solvent solution of the resin. Next, an adhesive layer (thickness 15 μm) was provided on the surface of the iodine transmission inhibition layer to obtain a polarizing plate with a phase difference layer having a composition of a protective layer (HC layer / COP film) / adhesive layer / polarizer / adhesive layer / phase difference layer (first liquid crystal orientation solidified layer / adhesive layer / second liquid crystal orientation solidified layer) / iodine transmission inhibition layer / adhesive layer. The total thickness of the obtained polarizing plate with a phase difference layer was 39.5 μm. The obtained polarizing plate with a retardation layer was subjected to the evaluations of (4) to (8) above. Furthermore, metal corrosion resistance was compared with Comparative Example 1 (described later) in which no iodine transmission suppression layer was formed. The results are shown in Tables 1 and 2.
[0236] [Example 2]
[0237] 97.0 parts of methyl methacrylate (MMA, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., trade name "methyl methacrylate monomer"), 3.0 parts of the copolymerizable monomer represented by the above general formula (1e), and 0.2 parts of a polymerization initiator (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., trade name "2,2′-azobis(isobutyronitrile)") were dissolved in 200 parts of toluene. Subsequently, a polymerization reaction was carried out for 5.5 hours while heating to 70°C under a nitrogen atmosphere to obtain a boron-containing acrylic resin solution (solid content concentration: 33%). The Tg of the obtained boron-containing acrylic polymer was 110°C and the Mw was 80,000. A polarizing plate with a phase difference layer was prepared in the same manner as in Example 1, except that the boron-containing acrylic polymer was used instead of the acrylic resin "B-811" and the thickness of the iodine transmission suppression layer was set to 0.3 μm. The obtained polarizing plate with a phase difference layer was subjected to the same evaluation as in Example 1. The results are shown in Tables 1 and 2.
[0238] [Example 3]
[0239] A polarizing plate with a retardation layer was prepared in the same manner as in Example 2 except that the thickness of the iodine transmission suppression layer was changed to 0.5 μm. The obtained polarizing plate with a retardation layer was subjected to the same evaluation as in Example 1. The results are shown in Tables 1 and 2.
[0240] [Example 4]
[0241] A polarizing plate with a phase difference layer was prepared in the same manner as in Example 1 except that a thermoplastic epoxy resin (manufactured by Mitsubishi Chemical Co., trade name "jER (registered trademark) 1256B40", Tg: 100°C, Mw: 45000) was used instead of the acrylic resin "B-811". The obtained polarizing plate with a phase difference layer was subjected to the same evaluation as in Example 1. The results are shown in Tables 1 and 2.
[0242] [Example 5]
[0243] A polarizing plate with a phase difference layer was prepared in the same manner as in Example 1 except that a thermoplastic epoxy resin (manufactured by Mitsubishi Chemical Co., trade name "jER (registered trademark) YX7200B35", Tg: 150°C, Mw: 30000) was used instead of the acrylic resin "B-811" and the thickness of the iodine transmission suppression layer was set to 0.3 μm. The obtained polarizing plate with a phase difference layer was subjected to the same evaluation as in Example 1. The results are shown in Tables 1 and 2.
[0244] [Example 6]
[0245] A polarizing plate with a retardation layer was prepared in the same manner as in Example 5 except that the thickness of the iodine transmission suppression layer was changed to 0.5 μm. The obtained polarizing plate with a retardation layer was subjected to the same evaluation as in Example 1. The results are shown in Tables 1 and 2.
[0246] [Example 7]
[0247] A polarizing plate with a phase difference layer was prepared in the same manner as in Example 1, except that a blend of 15 parts of "B-811" and 85 parts of a thermoplastic epoxy resin (Mitsubishi Chemical Co., trade name "jER (registered trademark) YX6954BH30") (in terms of solid content) was used instead of the acrylic resin "B-811". The Tg of the blend was 125°C and the Mw was 38,000. The obtained polarizing plate with a phase difference layer was subjected to the same evaluation as in Example 1. The results are shown in Tables 1 and 2.
[0248] [Example 8]
[0249] The polarizer side of the polarizing plate having the structure of protective layer (HC layer / COP film) / adhesive layer / polarizer obtained in 2. of Example 1 is coated with the resin blend used in Example 7 and dried to form an iodine transmission inhibition layer (thickness 0.5 μm) in the form of a solidified product of a coating film of an organic solvent solution of the resin. The liquid crystal orientation solidification layer A and the liquid crystal orientation solidification layer B are sequentially transferred to the surface of the iodine transmission inhibition layer in the same manner as in Example 1 to obtain a polarizing plate with a phase difference layer having the structure of protective layer (HC layer / COP film) / adhesive layer / polarizer / iodine transmission inhibition layer / adhesive layer / phase difference layer (first liquid crystal orientation solidification layer / adhesive layer / second liquid crystal orientation solidification layer) / adhesive layer. The obtained polarizing plate with a phase difference layer is subjected to the same evaluation as in Example 1. The results are shown in Tables 1 and 2.
[0250] [Example 9]
[0251] In addition to using the boron-containing acrylic polymer in Example 2, a laminate having a protective layer (HC layer / COP film) / adhesive layer / polarizer / iodine transmission inhibition layer is prepared in the same manner as in Example 8. Next, a blend of 15 parts of the boron-containing acrylic polymer in Example 2 and 85 parts of a thermoplastic epoxy resin (Mitsubishi Chemical Co., trade name "jER (registered trademark) YX6954BH30") (solid content conversion) is used, and in addition to this, a polarizing plate with a phase difference layer having a protective layer (HC layer / COP film) / adhesive layer / polarizer / iodine transmission inhibition layer / adhesive layer / phase difference layer (first liquid crystal orientation solidified layer / adhesive layer / second liquid crystal orientation solidified layer) / iodine transmission inhibition layer / adhesive layer is obtained in the same manner as in Example 1. The total thickness of the obtained polarizing plate with a phase difference layer is 40 μm. The obtained polarizing plate with a phase difference layer is subjected to the same evaluation as in Example 1. The results are shown in Table 2.
[0252] [Example 10]
[0253] The iodine transmission suppression layer disposed between the polarizer and the phase difference layer and adjacent to the polarizer is a blend of 15 parts of the boron-containing acrylic polymer obtained in Example 2 and 85 parts of a thermoplastic epoxy resin (Mitsubishi Chemical Co., trade name "jER (registered trademark) YX6954BH30") (solid content conversion), and a polarizing plate with a phase difference layer is obtained in the same manner as in Example 9. The total thickness of the obtained polarizing plate with a phase difference layer is 40 μm. The obtained polarizing plate with a phase difference layer is subjected to the same evaluation as in Example 1. The results are shown in Table 2.
[0254] [Example 11]
[0255] The iodine transmission inhibition layer formed between the polarizer and the phase difference layer and adjacent to the polarizer is formed between the polarizer and the phase difference layer and adjacent to the phase difference layer. In addition, a polarizing plate with a phase difference layer having a protective layer (HC layer / COP film) / adhesive layer / polarizer / adhesive layer / iodine transmission inhibition layer / phase difference layer (first liquid crystal orientation solidified layer / adhesive layer / second liquid crystal orientation solidified layer) / iodine transmission inhibition layer / adhesive layer is obtained in the same manner as in Example 10. The total thickness of the obtained polarizing plate with a phase difference layer is 40 μm. The obtained polarizing plate with a phase difference layer is provided for the same evaluation as in Example 1. The results are shown in Table 2.
[0256] [Example 12]
[0257] The same operation as in Example 9 was performed, and an iodine transmission inhibition layer was further formed between the polarizer and the phase difference layer and at a position adjacent to the polarizer. In addition, a polarizing plate with a phase difference layer having a protective layer (HC layer / COP film) / adhesive layer / polarizer / iodine transmission inhibition layer / adhesive layer / iodine transmission inhibition layer / phase difference layer (first liquid crystal orientation solidified layer / adhesive layer / second liquid crystal orientation solidified layer) / iodine transmission inhibition layer / adhesive layer was obtained in the same manner as in Example 11. The total thickness of the obtained polarizing plate with a phase difference layer is 40.5 μm. The obtained polarizing plate with a phase difference layer is provided for the same evaluation as in Example 1. The results are shown in Table 2.
[0258] [Comparative Example 1]
[0259] A polarizing plate with a retardation layer was prepared in the same manner as in Example 1 except that the iodine transmission suppression layer was not formed. The obtained polarizing plate with a retardation layer was subjected to the same evaluation as in Example 1. The results are shown in Tables 1 and 2.
[0260] [Comparative Example 2]
[0261] A polarizing plate with a retardation layer was prepared in the same manner as in Example 1 except that acrylic resin "B-723" (manufactured by Kusumoto Chemicals Co., Ltd., Tg: 54°C, Mw: 200,000) was used instead of acrylic resin "B-811". The obtained polarizing plate with a retardation layer was subjected to the same evaluation as in Example 1. The results are shown in Tables 1 and 2.
[0262] [Comparative Example 3]
[0263] A polarizing plate with a retardation layer was prepared in the same manner as in Example 1 except that a photocurable epoxy resin (Mitsubishi Chemical Co., trade name "jER (registered trademark) 828" was used instead of the acrylic resin "B-811" and "CPI100P" was used as a photopolymerization initiator. The obtained polarizing plate with a retardation layer was subjected to the same evaluation as in Example 1. The results are shown in Tables 1 and 2.
[0264] [Comparative Example 4]
[0265] A polarizing plate with a retardation layer was prepared in the same manner as in Example 1 except that a PVA resin (manufactured by Mitsubishi Chemical Co., trade name "GOHSENOL Z200", Tg: 80°C, Mw: 8800) was used instead of the acrylic resin "B-811". The obtained polarizing plate with a retardation layer was subjected to the same evaluation as in Example 1. The results are shown in Tables 1 and 2.
[0266] [Reference Example 1]
[0267] 1. Production of polarizing plate
[0268] In the same manner as in Example 1, a polarizing plate having a structure of protective layer (HC layer / COP film) / polarizer was obtained.
[0269] 2. Preparation of phase difference film constituting phase difference layer
[0270] 2-1. Polymerization of polyester carbonate resin
[0271] The polymerization was carried out using a batch polymerization apparatus consisting of two vertical reactors equipped with stirring blades and a reflux condenser controlled at 100° C. 29.60 parts by mass (0.046 mol) of bis[9-(2-phenoxycarbonylethyl)fluoren-9-yl]methane, 29.21 parts by mass (0.200 mol) of isosorbide (ISB), 42.28 parts by mass (0.139 mol) of spiroglycol (SPG), 63.77 parts by mass (0.298 mol) of diphenyl carbonate (DPC) and 1.19×10 calcium acetate monohydrate as a catalyst were added. -2 Mass parts (6.78×10 -5mol). After the reactor is replaced with nitrogen under reduced pressure, it is heated by a heat medium and stirring is started at the time when the internal temperature reaches 100°C. After 40 minutes from the start of heating, the internal temperature reaches 220°C, and the temperature is controlled to maintain the temperature and the pressure is reduced at the same time, so that it becomes 13.3kPa 90 minutes after reaching 220°C. The phenol vapor produced as a by-product accompanying the polymerization reaction is introduced into a reflux condenser at 100°C, and a small amount of monomer components contained in the phenol vapor is returned to the reactor, and the uncondensed phenol vapor is introduced into a condenser at 45°C for recovery. After nitrogen is introduced into the first reactor to temporarily restore it to atmospheric pressure, the oligomerized reaction liquid in the first reactor is moved to the second reactor. Next, heating and decompression in the second reactor are started, and after 50 minutes, the internal temperature becomes 240°C and the pressure becomes 0.2kPa. Thereafter, polymerization is carried out until the specified stirring power is reached. When a predetermined power was reached, nitrogen gas was introduced into the reactor to restore the pressure, and the produced polyester carbonate resin was extruded into water, and the strands were cut to obtain pellets.
[0272] 2-2. Preparation of phase difference film
[0273] After the obtained polyester carbonate resin (pellets) was vacuum dried at 80°C for 5 hours, a thin film forming device equipped with a single screw extruder (manufactured by Toshiba Machine Co., Ltd., cylinder set temperature: 250°C), a T-die (width 200mm, set temperature: 250°C), a cooling roller (set temperature: 120-130°C) and a winder was used to prepare a long strip of resin film with a thickness of 135μm. The obtained long strip of resin film was stretched in the width direction at a stretching temperature of 133°C and a stretching ratio of 2.8 times to obtain a retardation film with a thickness of 53μm. The Re(550) of the obtained retardation film was 141nm, Re(450) / Re(550) was 0.82, and the Nz coefficient was 1.12.
[0274] 3. Preparation of polarizing plate with phase difference layer
[0275] The phase difference film obtained in 2. is bonded to the surface of the polarizer of the polarizing plate obtained in 1. above with the aid of an acrylic adhesive (thickness 5 μm). At this time, the phase difference film is bonded in such a way that the absorption axis of the polarizer forms an angle of 45° with the slow axis of the phase difference film. Furthermore, an adhesive layer the same as in Example 1 is provided on the surface of the phase difference layer. Thus, a polarizing plate with a phase difference layer having a structure of a protective layer / adhesive layer / polarizer / adhesive layer / phase difference layer (stretched film of resin film) / adhesive layer is obtained. The total thickness of the obtained polarizing plate with a phase difference layer is 91 μm. The obtained polarizing plate with a phase difference layer is subjected to the same evaluation as in Example 1. The results are shown in Tables 1 and 2.
[0276] [Example 13]
[0277] A polarizing plate having a structure of a protective layer (HC layer / COP film) / adhesive layer / polarizer / iodine transmission inhibition layer / adhesive layer was obtained in the same manner as in Example 1, except that a phase difference layer was not formed. The total thickness of the obtained polarizing plate was 33.5 μm. The obtained polarizing plate was subjected to the same evaluation as in Example 1. The results are shown in Tables 1 and 2. It should be noted that this embodiment is a polarizing plate, which is different from the structure of a polarizing plate with a phase difference layer, and therefore, no comparison with Comparative Example 1 was made regarding metal corrosion.
[0278] [Table 1]
[0279]
[0280] [Table 2]
[0281]
[0282] * The blend is a blend of acrylic resin and epoxy resin
[0283] * Position A indicates the position between the phase difference layer and the adhesive layer, position B indicates the position between the polarizer and the phase difference layer and adjacent to the polarizer, position C indicates the position between the polarizer and the adhesive layer, and position D indicates the position between the polarizer and the phase difference layer and adjacent to the phase difference layer.
[0284] [evaluate]
[0285] It can be clearly seen from Table 1 that the polarizing plate and polarizing plate with phase difference layer of the embodiment of the present invention can make the ITO resistance value increase rate under high temperature and high humidity environment less than the specified value by forming a specified iodine transmission inhibition layer. It can be seen from this that the polarizing plate and polarizing plate with phase difference layer of the embodiment of the present invention can suppress the change of the resistance value of the electrode under high temperature and high humidity environment when applied to the image display device. In addition, the polarizing plate and polarizing plate with phase difference layer of the embodiment of the present invention can reduce the change of polarization degree under high temperature and high humidity environment, and have excellent durability. In addition, the polarizing plate and polarizing plate with phase difference layer of the embodiment of the present invention can also significantly suppress the metal corrosion and reflectivity increase under high temperature and high humidity environment. Furthermore, it can be clearly seen from Reference Example 1 that such ITO resistance value increase rate, polarization degree change, reflectivity increase and metal corrosion are very thin polarizing plates and polarizing plates with phase difference layer. It should be noted that when comparing Example 1 with Example 13, it can be clearly seen that the presence or absence of a liquid crystal orientation solidification layer (very thin phase difference layer) has no substantial effect on the effect of the present invention.
[0286] It is clear from Table 2 that the polarizing plates with phase difference layers of Examples 9 to 12 of the present invention can significantly suppress metal corrosion even when placed in a high temperature and high humidity environment for a long time (200 hours) by including two or three layers of iodine transmission inhibition layers. Therefore, it can be seen that the polarizing plates with phase difference layers of Examples 9 to 12 of the present invention can significantly suppress the corrosion of metal components when applied to image display devices.
[0287] Industrial Applicability
[0288] The polarizing plate of the present invention can be suitably used in liquid crystal display devices, organic EL display devices, and inorganic EL display devices. The polarizing plate with a retardation layer of the present invention can be suitably used as a circularly polarizing plate for liquid crystal display devices, organic EL display devices, and inorganic EL display devices.
[0289] Description of Reference Numerals
[0290] 10: Polarizing plate
[0291] 11: Polarizer
[0292] 12: Protective layer
[0293] 20: Phase difference layer
[0294] 30: Adhesive layer
[0295] 40: Iodine penetration inhibition layer
[0296] 100: Polarizing plate with phase difference layer
[0297] 101: Polarizing plate with phase difference layer
[0298] 102: Polarizing plate with phase difference layer
[0299] 103: Polarizing plate with phase difference layer
[0300] 104: Polarizing plate with phase difference layer
[0301] 105: Polarizing plate with phase difference layer
Claims
1. A polarizing plate comprising a polarizer, an iodine transmission suppression layer and an adhesive layer in this order, wherein the ITO resistance value increase rate is less than 100%, The iodine transmission inhibition layer is a solidified product or a thermally cured product of a coating film of an organic solvent solution of a resin. The resin constituting the iodine transmission suppression layer has a glass transition temperature of 85° C. or higher and a weight average molecular weight Mw of 25,000 or more and 150,000 or less. The resin constituting the iodine transmission inhibition layer comprises a copolymer obtained by polymerizing a monomer mixture, wherein the monomer mixture comprises more than 50 parts by weight of a (meth)acrylic acid monomer and more than 0 parts by weight and less than 50 parts by weight of a monomer represented by formula (1), In the formula, X represents a functional group containing a reactive group, and the reactive group is at least one reactive group selected from the group consisting of a vinyl group, a (meth)acryloyl group, a styryl group, a (meth)acrylamide group, a vinyl ether group, an epoxy group, an oxetane group, a hydroxyl group, an amino group, an aldehyde group, and a carboxyl group, and R 1 and R 2 each independently represents a hydrogen atom, an aliphatic hydrocarbon group which may have a substituent, an aryl group which may have a substituent, or a heterocyclic group which may have a substituent, and R 1 and R 2 Optionally, they are linked to each other to form a ring.
2. The polarizing plate according to claim 1, wherein The iodine transmission suppression layer is provided in two or more layers between the polarizer and the adhesive layer.
3. The polarizing plate according to claim 1 or 2, wherein: The thickness of the iodine transmission inhibition layer is 0.05 μm to 10 μm.
4. A polarizing plate with a phase difference layer, comprising the polarizing plate according to any one of claims 1 to 3 and a phase difference layer disposed between the polarizer and the adhesive layer; The phase difference layer is an orientation solidified layer of a liquid crystal compound having a circular polarization function or an elliptically polarization function; The ITO resistance value increase rate of the polarizing plate with a phase difference layer is 100% or less.
5. The polarizing plate with a phase difference layer according to claim 4, wherein: The phase difference layer is a single layer, The Re (550) of the phase difference layer is 100nm to 190nm. The angle formed by the slow axis of the phase difference layer and the absorption axis of the polarizer is 40° to 50°.
6. The polarizing plate with a phase difference layer according to claim 4, wherein: The phase difference layer has a stacked structure of an alignment solidified layer of a first liquid crystal compound and an alignment solidified layer of a second liquid crystal compound; The Re (550) of the alignment solidified layer of the first liquid crystal compound is 200 nm to 300 nm, and the angle formed by the slow axis and the absorption axis of the polarizer is 10° to 20°; The Re (550) of the alignment solidified layer of the second liquid crystal compound is 100 nm to 190 nm, and the angle formed by the slow axis thereof and the absorption axis of the polarizer is 70° to 80°. 7 . The polarizing plate with a retardation layer according to claim 4 , wherein the total thickness is 60 μm or less. 8 . An image display device comprising the polarizing plate according to claim 1 or the polarizing plate with a retardation layer according to claim 4 . 9 . The image display device according to claim 8 , which is an organic electroluminescent display device or an inorganic electroluminescent display device.
Citation Information
Patent Citations
Liq. crystalline (LC) material
DE19504224A1
Novel polymerizable liquid crystalline compounds
DE4408171A1
Liquid crystalline reticulated polysiloxanes
EP0066137A1
Picture display cell, method of forming an orientation layer on a substrate of the picture display cell and monomeric compounds for use in the orientation layer
EP0261712A1
Liquid crystal polyorganosiloxanes containing (meth)acryloxy groups
EP0358208A2
